Method for disintegrating water-insoluble carbohydrates

By adding water-soluble polysaccharides to form a complex and decompose it with a food mixer, the problem of low decomposition efficiency of water-insoluble carbohydrates is solved, the decomposition efficiency is improved and the adhesion phenomenon is reduced, and its application in the food and non-food industries is expanded.

JP7625277B2Active Publication Date: 2025-02-03NAT AGRI & FOOD RES ORG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022186622
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-25
Filing Date
2022-11-22
Publication Date
2025-02-03
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently decompose water-insoluble carbohydrates, resulting in limited application in food and non-food industries, especially in the 3D food printing process, which easily adheres to the equipment, affecting operation efficiency.

Method used

By adding water-soluble polysaccharides to the decomposition process of water-insoluble carbohydrates, a complex containing water-soluble polysaccharides and water-insoluble carbohydrates is formed, and the decomposition is performed using a food mixer or food mixer to reduce the possibility of reaggregation and improve the decomposition efficiency.

Benefits of technology

The efficient decomposition of water-insoluble carbohydrates is achieved, reducing adhesion in 3D food printing, improving operational efficiency, and providing multifunctional materials for the food and non-food industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625277000007
    Figure 0007625277000007
  • Figure 0007625277000008
    Figure 0007625277000008
  • Figure 0007625277000009
    Figure 0007625277000009
Patent Text Reader

Abstract

Disintegrating water-insoluble carbohydrates. The present disclosure provides a complex containing a water-soluble polysaccharide and a water-insoluble carbohydrate. In the present disclosure, it has been found that the coexistence of a polysaccharide that interacts with the water-insoluble carbohydrate during the disintegration step of the water-insoluble carbohydrate is effective in providing a useful disintegrated water-insoluble carbohydrate product.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a complex comprising a water-soluble polysaccharide and a water-insoluble carbohydrate, and a method for producing the same. [Background technology]

[0002] Known technologies for disintegrating cellulose fibers to produce cellulose nanofibers include chemical methods such as TEMPO oxidation and phosphoric acid esterification, which mainly use plant-derived pulp as the raw material, and enzymatic hydrolysis, as well as methods using grinders, homogenizers, and underwater counter-impingement methods.

[0003] It is expected that high-quality cellulose fibers with a low paper texture can be obtained by disintegrating bacterial cellulose, and for example, a technique is known in which bacterial cellulose is treated with a pulp disintegrator, then subjected to a pressure disintegration treatment with a homogenizer, and then added to chocolate drinks, crumb paste, ice cream, tofu, kamaboko, hamburger patties, sausages, bean paste, etc. Also known is a method in which nata de coco is treated with a blender at 20,000 rpm for 10 minutes, followed by a high-pressure homogenization treatment (10 passes at a maximum of 600 bar), or a method in which it is disintegrated with a high-shear blender and then further treated with an ultrasonic device.

[0004] The cellulose disintegrates obtained by disintegrating cellulose are expected to have various applications in the food industry. In addition, disintegrating water-insoluble carbohydrates such as plant stems and leaves, which contain cellulose as the main component, chitin, and crustacean shells, which contain chitin as the main component, is attracting much attention because it can be used not only in the food industry but also in non-food industries, such as plastics, fibers, membranes, and paper. Summary of the Invention [Means for solving the problem]

[0005] The inventors conducted extensive research based on the hypothesis that the appearance of new cellulose surfaces that may occur during the disintegration process of water-insoluble carbohydrates, such as cellulose, causes association between nearby cellulose molecules and promotes entanglement of the fibers, resulting in poor disintegration. As a result, they found that the coexistence of polysaccharides that interact with water-insoluble carbohydrates during the disintegration process of water-insoluble carbohydrates is effective in providing a useful disintegrated product of water-insoluble carbohydrates.

[0006] Thus, the present disclosure provides: (Item 1) A complex comprising a water-soluble polysaccharide and a water-insoluble carbohydrate. (Item 2) The complex described in the above item, wherein the water-insoluble carbohydrate is disintegrated in the presence of the water-soluble polysaccharide dissolved in water. (Item 3) The complex according to any one of the preceding items, wherein the water-soluble polysaccharide comprises xylan or a derivative thereof, β-glucan or a derivative thereof, mannan or a derivative thereof, a water-soluble cellulose derivative or a salt thereof, chitosan or a derivative thereof, alginic acid or a salt thereof or a derivative thereof, carrageenan, gellan gum, pectin or a partial structure thereof or a derivative thereof, or any combination thereof. (Item 4) The complex according to any one of the preceding items, wherein the β-glucan or a derivative thereof comprises (1-3) or (1-4) β-glucan. (Item 5) The complex according to any one of the preceding claims, wherein the β-glucan or derivative thereof comprises tamarind seed gum. (Item 6) The complex of any one of the preceding claims, wherein the water-insoluble carbohydrate comprises bacterial cellulose. (Item 7) The complex according to any one of the preceding claims, wherein the water-insoluble carbohydrate is disintegrated by a food blender or food mixer. (Item 8) A complex described in any one of the above items, wherein when compared to a composition in which the water-insoluble carbohydrate is mixed after disintegration of the water-insoluble carbohydrate, the complex has a larger volume than the composition. (Item 9) Item 3. The complex of any one of the preceding items, wherein the water-soluble polysaccharide is a (1-3),(1-4) β-glucan and the water-insoluble carbohydrate is cellulose. (Item 10) A binding improver for a subject to be bound, comprising the complex according to any one of the above items. (Item 11) An adhesion suppressant to be mixed, comprising the complex described in any one of the above items. (Item 12) A texture-changing agent for food or beverage to be mixed, comprising the complex according to any one of the above items. (Item 13) A viscosity-increasing, stability-changing agent to be mixed, comprising the complex according to any one of the preceding items. (Item 14) A water permeation suppression or control agent comprising the complex according to any one of the preceding items. (Item 15) A biodegradable or biocompatible material comprising the composite material according to any one of the above items. (Item 16) A paper, fiber, or plastic modifier comprising the composite according to any one of the preceding items. (Item 17) A fiber texture improver for food and beverages, comprising the complex described in any one of the above items. (Item 18) A composition having reduced disintegration in water, comprising a composition comprising a complex described in any one of the above items bound to a water-insoluble particle, and coated with a complex described in any one of the above items or an inhibitor or control agent described in any one of the above items. (Item 19) The composition of any one of the preceding items, wherein the water-insoluble particles include particles comprising at least one material selected from starch, cellulose, or β-1,3-glucan. (Item 20) A food or drink obtained from the complex described in any one of the above items. (Item 21) The food or beverage according to any one of the above items, comprising a confectionery, a noodle, a cream, an emulsion, a 3D printed food, a meat substitute, a lipid substitute, a food binder, a dispersion medium, a thickening agent, a paste preparation agent, a dye adsorbent, a water absorption regulator, and an agar mixed gel. (Item 22) A food or beverage for use with a 3D food printer, comprising a mixture of the complex described in any one of the above items and a food or beverage. (Item 23) A food or drink comprising the complex according to any one of the above items and a gelling agent. (Item B1) The complex according to any one of the preceding items, for improving the binding property of an object to be bound. (Item B2) The composite according to any one of the above items for suppressing the adhesion of a mixture. (Item B3) The complex according to any one of the preceding items, for changing the texture of a food to be mixed therewith. (Item B4) A complex according to any one of the preceding items for changing the thickening stability of a subject to be mixed. (Item B5) 2. The composite of claim 1, for inhibiting or controlling water permeation. (Item B6) 2. A composite according to any one of the preceding items for use as a biodegradable or biocompatible material. (Item B7) 2. The composite of any one of the preceding items for use as a modifier for paper, textiles, or plastics. (Item A1) A method for producing a complex comprising a water-soluble polysaccharide and a water-insoluble carbohydrate, comprising the steps of: A step of disintegrating the water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water. A method comprising: (Item A2) The method according to any one of the preceding items, wherein the complex improves the binding property of a food material. (Item A3) The method according to any one of the preceding items, wherein the water-soluble polysaccharide comprises xylan or a derivative thereof, β-glucan or a derivative thereof, mannan or a derivative thereof, a water-soluble cellulose derivative or a salt thereof, chitosan or a derivative thereof, alginic acid or a salt thereof or a derivative thereof, carrageenan, gellan gum, pectin or a partial structure thereof or a derivative thereof, or any combination thereof. (Item A4) The method according to any one of the preceding items, wherein the β-glucan or its derivative comprises (1-3) or (1-4) β-glucan. (Item A5) The method according to any one of the preceding claims, wherein the β-glucan or derivative thereof comprises tamarind seed gum. (Item A6) Item 11. The method of any one of the preceding items, wherein the water-insoluble carbohydrate comprises bacterial cellulose. (Item A7) The method according to any one of the preceding claims, wherein the water-insoluble carbohydrates are macerated by a food blender or food mixer. (Item A8) The method according to any one of the preceding items, wherein the complex has a larger volume than a composition mixed with the water-insoluble carbohydrate after disintegration of the water-insoluble carbohydrate. (Item A9) The method according to any one of the preceding claims, wherein the concentration of the water-insoluble carbohydrate at the time of disintegration is at least about 0.001 as a ratio to the combined weight of the water-insoluble carbohydrate, the water, and the water-soluble polysaccharide. (Item A10) A method for producing food and beverages for a 3D food printer, comprising: disintegrating the water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water; a step of mixing the complex containing the water-soluble polysaccharide and the water-insoluble carbohydrate obtained by the disintegration step with any food or drink raw material; A method comprising: (Item A11) 1. A method for forming a highly homogeneous gel, comprising the steps of: disintegrating the water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water; a step of mixing the complex containing the water-soluble polysaccharide and the water-insoluble carbohydrate obtained by the disintegration step with a gelling agent to obtain a mixture; dispersing the mixture in a solvent; subjecting the mixture to a heating and / or cooling treatment; A method comprising: (Item A12) 2. The method according to any one of the preceding claims, wherein the heating and / or cooling treatment comprises laser processing.

[0007] It is contemplated that one or more of the above features may be provided in combinations other than those specifically stated.Further embodiments and advantages of the present disclosure will be recognized by those skilled in the art upon reading and understanding the following detailed description, if necessary.

[0008] Furthermore, features and notable actions and effects of the present disclosure other than those described above will become apparent to those skilled in the art by referring to the following description of the preferred embodiments of the present invention and the drawings. Effect of the Invention

[0009] The disintegrated water-insoluble carbohydrates obtained by the method disclosed herein can be applied to a variety of substances and processes, and also have the effect of reducing adhesion to utensils, making them useful as materials in automated cooking processes, particularly 3D food printers.

[0010] This technology can also provide new materials that can be used in the manufacture of foods, fibers, daily necessities, etc. In particular, in food processing, it can be used as a low-calorie or calorie-free lipid substitute, meat substitute, emulsion material, sauce, dressing, cream, etc. It can also be used to adjust the texture and as a binding material for ingredients, and can also be used as a dietary fiber source due to the disintegrated water-insoluble carbohydrates and polysaccharides that coexist during disintegration. Furthermore, this technology can be used to manufacture foods such as "Smile Care Food" to maintain the quality of life for people with problems in chewing and swallowing. It is also useful for expanding the range of application of materials by controlling the water movement in 3D food printers, improving the dispersibility of powders, and controlling paste properties through the retention of ingredients such as pigments, and preventing adhesion to containers during kneading.

[0011] Furthermore, as a non-edible material with properties such as adhesiveness, moldability, biodegradability, and biocompatibility, it is expected to be used in plastic substitutes, films, powders, fibers, solid storage materials, and so on. [Brief description of the drawings]

[0012] [Figure 1A] FIG. 1A is a graph showing the screen transmittance of a disintegrate (8-fold diluted) of nata de coco cellulose in the presence of polysaccharides. [Figure 1B] FIG. 1B is a photograph showing the difference in dispersibility between the control group (BC+xyloglucan (added after disintegration)) and the test group (BC+xyloglucan (added before disintegration)). [Diagram 2] FIG. 2 is a photograph showing a colored sample of a complex according to one embodiment of the present disclosure (left) and a product cooked with the same (right). [Diagram 3] 3 is a photograph showing an example of adhesion during a kneading operation of a complex according to an embodiment of the present disclosure. Left: control sample, right: sample with added β-glucan and added macerated material [Figure 4] FIG. 4 is a photograph showing the baked control sample (left) and the baked sample with added β-glucan and lysate (right). [Diagram 5]FIG. 5 is a photograph showing thin films derived from the lysate with the addition of β-glucan (left) and from the lysate with the addition of chitosan (right). [Figure 6] Figure 6 shows photographs of the gel produced after the addition of chitosan and the disintegration (left), and the gel produced after the addition of sodium alginate mixed with starch and the disintegration (right). [Figure 7] FIG. 7 is a photograph showing a thick soy sauce made from a composite according to an embodiment of the present disclosure. [Figure 8] FIG. 8 shows a schematic diagram of the syringe installation mode (left) and a photograph of the syringe after installation (right). [Figure 9] FIG. 9 is a photograph of the composite (gel) according to one embodiment of the present disclosure upon injection. [Figure 10] FIG. 10 is a photograph showing the molded product after injection (top left: string-like, top right: swirl-like) and the molded product after heating (bottom). [Figure 11] Figure 11 is a photograph showing rice starch mixed with water (left) and rice starch mixed with BC β-glucan-added and disintegrated material (right). The photographs are arranged at an angle so that the top is higher and the bottom is lower. In the sample on the left, the liquid mixture flows and moves to one side. [Figure 12] FIG. 12 is a photograph showing the molded product (on a plate) made by mixing rice starch with BC β-glucan-added and disintegrated material. [Figure 13] FIG. 13 is a photograph showing the molded product of FIG. 12 taken out after being steamed and heated in a microwave oven. [Figure 14] FIG. 14 is a photograph showing a meat substitute food to which water was added (left) and a molded product to which BC β-glucan was added and disintegrated (right). [Figure 15] FIG. 15 is a photograph showing the molded product after baking in a toaster oven. [Figure 16] FIG. 16 is a set of photographs showing the molded products (left: (1), left: (2), right: (3), right: (4)) before the heat treatment. [Figure 17]FIG. 17 is a set of photographs showing the molded products after heating (lower left: (1), upper left: (2), upper right: (3), lower right: (4)). [Figure 18] FIG. 18 is a photograph showing the molded product after baking in a toaster oven. [Figure 19] Figure 19 is a photograph showing a whipped cream-like food product. Left: after whipping, right: after extrusion and placement. [Figure 20] Figure 20 is a photograph showing the state of floating of lumpy ground material when the grinding time is changed. From left to right, the samples are after grinding for 5 seconds, 10 seconds, 15 seconds, 20 seconds, 25 seconds, and 30 seconds. [Figure 21] FIG. 21 is a photograph showing a kneaded product of BC disintegrated material and rice starch (left) and a noodle-like food product after boiling (right). [Figure 22] FIG. 22 is a photograph showing rice starch and BC disintegrated material mixed and arranged in a granular form (left) and the granular food product after boiling (right). [Figure 23] Figure 23 is a photograph showing a mixture of potato powder and BC disintegrate (left) and a dumpling-like food after boiling (right). Only the one on the far right in the right picture shows the dumpling-like food before boiling. [Figure 24] FIG. 24 is a photograph showing an extrusion of potato paste. [Diagram 25] FIG. 25 is a photograph showing short noodles that have been boiled and then cooled under running water on a sieve. [Figure 26] FIG. 26 is a photograph showing the state of a soybean flour suspension 5 hours after the addition of water (left) or β-glucan-added / disintegrated material (1-3) or (1-4) obtained from BC (right) to the suspension. [Figure 27] FIG. 27 is a photograph showing the result of adding water (left) or β-glucan (1-3) and (1-4) added / disintegrated products (right) obtained from BC to a curcumin dispersion and centrifuging the mixture. [Figure 28] Figure 28 is a photograph showing a disk-shaped dry composition made of glucan (viewed from the side). The hemispherical convex part at the top center of the sample shows the state in which a water droplet placed on top does not penetrate and remains inside. [Figure 29]FIG. 29 is a photograph showing a rice straw-paper-like membrane. [Diagram 30] FIG. 30 is a photograph of heated rice flour to which a complex according to an embodiment of the present disclosure has been added. [Diagram 31] FIG. 31 is a graph showing the sedimentation rate of weak flour to which a complex according to an embodiment of the present disclosure has been added. [Diagram 32] FIG. 32 is a graph showing the sedimentation rate of rice flour to which a complex according to an embodiment of the present disclosure has been added. [Diagram 33] Figure 33 is a graph showing the sedimentation rate of weak flour and rice flour with added xanthan gum. Data is shown for each xanthan gum concentration, with the left bar representing weak flour and the right bar representing rice flour. [Diagram 34] FIG. 34 is a photograph showing the dispersion state of the complex according to an embodiment of the present disclosure, or weak flour and rice flour to which xanthan gum has been added. [Diagram 35] The left side of Fig. 35 shows a photograph of a syringe filled with a slurry obtained by mixing a complex according to an embodiment of the present disclosure with weak flour, and the right side of Fig. 35 shows a photograph of the weak flour slurry ejected from the syringe. [Diagram 36] FIG. 36 is a photograph showing a sheet-shaped molded product of a slurry obtained by mixing a complex according to one embodiment of the present disclosure with weak flour, and a sheet-shaped molded product prepared by mixing turmeric powder or parsley powder with the slurry. [Figure 37] FIG. 37 is a graph showing an increase in hardness of vegetable paste by adding a complex according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present disclosure will be described below while showing the best mode. Throughout this specification, the expression of the singular form should be understood to include the concept of the plural form, unless otherwise specified. Therefore, the singular article (for example, in the case of English, "a", "an", "the", etc.) should be understood to include the concept of the plural form, unless otherwise specified. In addition, it should be understood that the terms used in this specification are used in the sense commonly used in the field, unless otherwise specified. Therefore, unless otherwise defined, all technical terms and scientific and technical terms used in this specification have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. In case of conflict, the present specification (including definitions) will take precedence.

[0014] The following provides definitions of terms particularly used in this specification and / or explains basic technical content as appropriate.

[0015] As used herein, "about" means ±10% of the preceding numerical value.

[0016] In this specification, the term "disintegration" refers to the process of defibrating or loosening water-insoluble carbohydrates, such as bacterial cellulose and pulp fibers, to form a slurry. The disintegrated material is also referred to as a "disintegrated product."

[0017] As used herein, the term "polysaccharide" refers to a polymer of multiple monosaccharides, and in the present disclosure typically includes any monosaccharide having five or more sugars. The monosaccharides used in polysaccharides are not particularly limited, but include, for example, glucose, galactose, fructose, xylose, arabinose, galacturonic acid, glucuronic acid, mannose, glucosamine, N-acetylglucosamine, rhamnose, anhydrogalactose, and the like, and may include those composed of one or more types of those with modified side chains. The binding patterns of monosaccharides include linear, branched, and cyclic, as well as those that have multiple of these patterns and those that are bound to substances other than sugars, such as other sugars, proteins, or lipids.

[0018] In this specification, the term "water-soluble polysaccharide" refers to a water-soluble polysaccharide, and although there are many types of natural compounds, in addition to natural products, artificially synthesized compounds may be used in this specification. In this specification, the water-soluble polysaccharide also includes polysaccharides that are not water-soluble as they are, but become water-soluble after treatment with an acid or alkali, or after heat treatment, etc. Examples include, but are not limited to, xylan or a derivative thereof (including those substituted with glucuronic acid residues, arabinose residues, etc.), β-glucan or a derivative thereof ((1-3), (1-4) β-glucan, xyloglucan, xanthan gum, tamarind seed gum (main component: xyloglucan), etc.), mannan or a derivative thereof (galactomannan, etc.), water-soluble cellulose derivatives or salts thereof (including polysaccharides obtained by chemically modifying cellulose, such as carboxymethylcellulose salts, methylcellulose, and hydroxypropylmethylcellulose), chitosan or a derivative thereof (partially deacetylated chitin, etc.), alginic acid or a salt thereof or a derivative thereof, carrageenan, gellan gum, pectin or a partial structure thereof or a derivative thereof, and any combination thereof.

[0019] In this specification, "carbohydrate" basically refers to a substance whose main component is monosaccharide, and edible carbohydrates include digestible sugars and dietary fiber. There are many types of carbohydrate compounds that exist as natural products, but the carbohydrates used in this specification may be artificially synthesized or may exist in a state containing substances other than carbohydrates. In addition, carbohydrates in this specification also include inedible plant cell walls, intracellular or extracellular polysaccharides of microorganisms, storage polysaccharides in seeds, roots, tubers, etc., animal intracartilage polysaccharides, animal extracellular matrix polysaccharides, and extracellular skeletal polysaccharides.

[0020] In this specification, the term "water-insoluble carbohydrate" refers to water-insoluble carbohydrates in general. Water-insoluble carbohydrates include, for example, plant tissues mainly composed of water-insoluble cellulose, such as bacterial cellulose (natadecoco), starch, chitin, chitosan, paramylon, peptidoglycan, mannan, plant cellulose (pulp), and plant fiber (vegetable powder, etc.), crab shells, shrimp shells, animal tissues, insect powders, algae bodies, filamentous fungal bodies, yeast bodies, and bacterial bodies (Bacillus subtilis natto bodies, lactic acid bacteria bodies, etc.). Water-insoluble carbohydrates may also be water-insoluble substances composed of multiple types of carbohydrates.

[0021] As used herein, the term "complex" refers to a substance formed by the combination of multiple structural units, and the complex state here refers to a state in which a water-soluble polysaccharide dissolved in water or an aqueous solution exists near the surface of a water-insoluble carbohydrate in water or an aqueous solution, i.e., near the solid-liquid interface, through interactions mainly based on non-covalent bonds.

[0022] As used herein, "in the presence of" refers to the presence of a water-insoluble carbohydrate and a water-soluble polysaccharide in the same system at the same time, and refers to the presence of the water-soluble polysaccharide in a dissolved state when the disintegration operation of the water-insoluble carbohydrate of the present disclosure is performed. When the disintegration operation of the present disclosure is performed, at least a part of the water-soluble polysaccharide in the presence of the water-insoluble carbohydrate is in a state in which it can newly form a complex with the water-insoluble carbohydrate. An embodiment in which a water-soluble polysaccharide is added after the disintegration operation of the water-insoluble carbohydrate cannot be said to be "in the presence of" as used herein, and an embodiment in which a water-soluble polysaccharide that has already formed a complex with a water-insoluble carbohydrate is disintegrated cannot be said to be disintegration "in the presence of" as used herein.

[0023] In this specification, "adhesiveness" means the property of adhesion between substances such as meat pieces, soybean flour, potato flour, etc. when they are kneaded with water or fat, and indicates the degree of adhesion when meat or fat is kneaded. Adhesiveness can be evaluated, for example, by binding the substances to be bound and then vibrating them to measure the degree of disintegration.

[0024] In this specification, "adhesiveness" refers to the property of sticking, and is also called adhesiveness or stickiness. Adhesiveness can be evaluated, for example, by measuring the strength of stickiness when the paste is stirred, visually checking the degree of adhesion to a stirring tool or container, or by contacting a probe with the paste after molding and measuring the stress when the probe is pulled away.

[0025] In this specification, "thickening stability" refers to increasing the viscosity and increasing the stability of the sol-gel, and can stabilize liquid foods by increasing the viscosity, stabilize the dispersibility of solids, or stabilize the shape by gelation to impart texture. Thickening stability can be evaluated, for example, by measuring the viscosity, flow properties, and viscoelasticity.

[0026] In this specification, the term "biodegradable material" refers to a polymer that is decomposed into low molecular weight compounds that do not have a negative impact on the environment by the action of microorganisms present in soil or water in nature, or by the action of these microorganisms combined with chemical reactions, physical destruction, etc. in the environment. Biodegradability can be evaluated, for example, by dispersing the material in a microbial culture medium and observing a decrease in turbidity as the microorganisms grow.

[0027] In this specification, the term "biocompatible material" refers to a material that, when it comes into contact with a living body, has properties that do not cause adverse physical or chemical effects on the living body and do not cause problems such as physiological rejection reactions such as immune reactions. Biocompatibility can be confirmed, for example, by conducting biochemical tests, cell tests, animal tests, human tests, etc. depending on the application.

[0028] In this specification, the "water permeability" of a material refers to the process in which, when the material comes into contact with water, the material absorbs water from the contact surface and the water soaks into the material. Water permeability is affected by the structure of the material, such as whether or not a flow path is provided, and can be evaluated, for example, by placing a water droplet on the interface between the material and a gas and observing whether or not the water droplet quickly penetrates into the material.

[0029] In this specification, the term "food blender" or "food mixer" refers to a so-called household blender or mixer available in the general distribution process, and includes, for example, a blender or mixer with a processing capacity of about 20 liters or less per processing and about 50 liters or less per hour when continuously processing, which is sold to households, cake shops, food manufacturing shops, restaurants, small food manufacturing shops, etc. at home electronics stores and online sales sites. Examples of food blenders or food mixers include devices or equipment for blending and / or mixing food for one to a dozen people. Industrial manufacturing machines with a processing capacity of, for example, more than about 20 liters per processing or more than about 50 liters per hour when continuously processing, such as blenders, mixers, high-pressure processing devices, ultrasonic crushing devices, and other test and research devices, and industrial devices such as refiners and fiberizers for the pulp industry, mass colloiders (Masuko Sangyo Co., Ltd.), ball mills, and bead mills are not included.

[0030] As used herein, "texture" refers to the skin sensation in the oral cavity, including the teeth and tongue, among the five senses felt when eating or drinking food. Specifically, this includes the chewiness, the feel on the tongue, and the feeling down the throat. Together with other senses such as taste, it is an important element in constituting "deliciousness." For example, texture can be evaluated using instrumental measurement methods using a dynamic viscoelasticity measuring device, a chewing model, etc., in addition to human tests.

[0031] In this specification, a "modifier" for paper etc. refers to an additive that, when added to a target substance, improves the properties of that substance compared to before the addition; for example, a paper modifier can increase the smoothness of paper, improve the mechanical properties, impart water repellency, change the color tone, or change the biodegradability.

[0032] In this specification, "film formability" refers to the property when forming a film, and is also called film formability. For example, a material with high film formability can reduce problems in film formation, such as shrinkage into an undesired shape when preparing a film, failure to obtain a non-uniform and uneven flat surface, and poor peelability from the base screen or stand. This property depends on the film formation method, and film formability can also be improved by adding auxiliary materials.

[0033] In this specification, "highly dispersible" refers to a property in which particles dispersed in a solute such as water, an aqueous solution, or a sol, or water-insoluble molecules such as colloids, do not or are unlikely to aggregate or float or settle over time and lose their initial dispersed state.

[0034] (Preferred embodiment) Preferred embodiments of the present disclosure are described below. The embodiments provided below are provided for a better understanding of the present disclosure, and the scope of the present disclosure should not be limited to the following description. Therefore, it is clear that a person skilled in the art can make appropriate modifications within the scope of the present disclosure in light of the description in this specification. In addition, the following embodiments of the present disclosure can be used alone or in combination.

[0035] In one aspect of the present disclosure, a complex is provided that includes a water-soluble polysaccharide and a water-insoluble carbohydrate. In one embodiment, the complex of the present disclosure is obtained by disintegrating a water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water. In this specification, the complex of the present disclosure may be referred to as NP or nata puree, particularly when the desugared product of nata de coco is used as a raw material.

[0036] Examples of water-insoluble carbohydrates that can be used in the complex of the present disclosure include plant tissues that are mainly composed of water-insoluble cellulose, such as bacterial cellulose (natadecoco), starch, chitin, chitosan, paramylon, peptidoglycan, mannan, plant cellulose (pulp), and plant fibers (vegetable powder, etc.), crab shells, shrimp shells, animal tissues, insect powder, algae cells, filamentous fungal cells, yeast cells, and bacterial cells (Bacillus subtilis natto cells, lactic acid bacteria cells, etc.). Water-insoluble carbohydrates such as plant cellulose and bacterial cellulose are prone to entanglement during disintegration and have low disintegration properties, so that when only the water-insoluble carbohydrates are suspended in water, they cannot be disintegrated using a food blender or food mixer, and it was necessary to disintegrate them using special devices such as high-power grinders and homogenizers for the pulp industry, high-pressure processing devices, and ultrasonic processing devices. In the present disclosure, a technology is provided that allows water-insoluble carbohydrates that could only be disintegrated using such special devices to be easily disintegrated using a food blender or food mixer.

[0037] Bacterial cellulose is in a gel-like form, produced as nata de coco, and the like. If necessary, the material can be used after removing coexisting substances such as bacteria and washing or cutting according to a known method. In the case of a cut product distributed in a stabilizer such as sugar solution, the material can be desugared and washed as necessary. In addition, raw materials distributed as dried products are preferably made to have absorbed water in the disintegration process. Plant cellulose (pulp) is a cut product of plant tissue derived from wood, herbs, algae, etc., and more preferably, a raw material with an improved cellulose content from which at least a portion of components coexisting with cellulose, such as cell wall components and intracellular components, have been removed. Similarly, with other water-insoluble carbohydrates, it is desirable to improve disintegration efficiency by cutting into a shape suitable for grinding and increasing the carbohydrate content.

[0038] The concentration of the water-insoluble carbohydrates at the time of disintegration can be about 0.001 to about 0.5, more preferably about 0.001 to about 0.3, as a ratio to the combined weight of the water-insoluble carbohydrates, water, and water-soluble polysaccharides.

[0039] In one embodiment of the present disclosure, the water-insoluble carbohydrate can be disaggregated in a food blender or food mixer by coexisting with a water-soluble polysaccharide dissolved in water during disaggregation, and the complex thus obtained contains a mixture of water-insoluble carbohydrate and water-soluble polysaccharide. In one embodiment, in the method of the present disclosure, the disaggregation of the water-insoluble carbohydrate may be performed under harsher conditions using an industrial machine such as a ball mill. In another embodiment, the complex obtained by disaggregating the water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water using a food blender or food mixer can be further treated with an industrial machine such as a ball mill to obtain a finer disaggregate. This is expected to further reduce the risk of clogging the flow path when the complex of the present disclosure is passed through a flow path.

[0040] In one embodiment of the present disclosure, one or more kinds of water-soluble polysaccharides can be added during disintegration of the water-insoluble carbohydrate. In one embodiment of the present disclosure, the water-soluble polysaccharide is preferably a polysaccharide that interacts with the surface of water-insoluble cellulose, and examples thereof include, but are not limited to, xylan or its derivatives (including those substituted with glucuronic acid residues, arabinose residues, acetyl groups, 4-O-methylglucuronic acid residues, feruloyl groups, etc.), β-glucan or its derivatives ((1-3), (1-4) β-glucan, xyloglucan, xanthan gum, tamarind seed gum (main component: xyloglucan), etc.), mannan or its derivatives (galactomannan, etc.), water-soluble cellulose derivatives or their salts (including polysaccharides obtained by chemically modifying cellulose, such as carboxymethylcellulose salts, methylcellulose, and hydroxypropylmethylcellulose), chitosan or its derivatives (partially deacetylated chitin, etc.), alginic acid or its salts or their derivatives, carrageenan, gellan gum, pectin or its partial structures or their derivatives, and any combination thereof. In one embodiment, the β-glucan or its derivatives may include (1-3), (1-4) β-glucan, and not only purified (1-3), (1-4) β-glucan but also extracts containing (1-3), (1-4) β-glucan from barley, wheat, oats, etc. may be used as the water-soluble polysaccharide of the present disclosure. When obtaining such an extract, it is necessary to inactivate the (1-3), (1-4) β-glucan decomposition enzyme present in barley, etc., and a method of obtaining an extract by roasting barley, etc. and then grinding it, or by grinding it and then heating it, and obtaining an extract, is effective. In addition, the extract may contain sugars other than (1-3), (1-4) β-glucan, such as water-soluble polysaccharides such as xylan derivatives. Some water-soluble polysaccharides are easily available as thickening stabilizers, but extracts containing (1-3),(1-4) β-glucan from barley, wheat, oats, etc., and extracts containing xylan derivatives from rice bran and wheat bran are water-soluble polysaccharides that can be easily obtained from food materials, making it possible to easily produce the complex according to the present disclosure at home or at a small-scale production site.

[0041] In one embodiment of the present disclosure, these water-soluble polysaccharides can be dissolved or highly swollen by adding an acid or alkali or heating as necessary, and then allowed to coexist with the water-insoluble carbohydrate at the time of disintegration. In one embodiment of the present disclosure, the water-soluble polysaccharide can be subjected to sterilization techniques for wet foods, such as autoclave sterilization or retort sterilization, to improve shelf life and maintain quality. The effective weight ratio of the water-soluble polysaccharide to the water-insoluble carbohydrate at the time of disintegration varies depending on the characteristics of the interaction between the water-soluble polysaccharide and the water-insoluble carbohydrate, the characteristics of the partial structure of the water-soluble polysaccharide involved in the interaction, the purity of the carbohydrate in the water-insoluble carbohydrate, the potentially exposed amount of the surface involved in the interaction in the water-insoluble carbohydrate, the degree of surface exposure depending on the treatment conditions at the time of disintegration, the influence of coexisting substances in the system at the time of disintegration, and the like. For example, in one embodiment, the water-soluble polysaccharide can be added in an amount of about 0.01 to about 2 in terms of weight ratio to the water-insoluble carbohydrate. When the water-insoluble carbohydrate is disintegrated, it is sufficient that the water-insoluble carbohydrate and the water-soluble polysaccharide dissolved in water coexist, and other substances can be added as necessary. For example, when the complex of the present disclosure is used as a food, seasonings and various auxiliary ingredients can be added when the complex of the present disclosure is obtained.

[0042] In one embodiment of the present disclosure, the water-insoluble carbohydrate can be disintegrated by a food blender or food mixer in the presence of a water-soluble polysaccharide dissolved in water, and the treatment time can be about 1 second to about 120 minutes, preferably about 5 seconds to about 60 minutes, and more preferably about 10 seconds to about 10 minutes. In one embodiment, the treatment with a food blender or food mixer can be divided into multiple treatments of about 10 seconds, about 20 seconds, or about 30 seconds, for example, for a total of about 1 minute, about 5 minutes, about 7 minutes, or about 10 minutes, in order to avoid heating the machine. In one embodiment, the treatment temperature can be appropriately changed depending on the characteristics of the water-soluble polysaccharide to be coexisted. In one embodiment, when water-insoluble cellulose is used as the water-insoluble carbohydrate to be disintegrated, it is stable at about 0°C to about 100°C, where water molecules are liquid, and can be treated in this temperature range when the effects of water-soluble polysaccharides and other additives are not taken into consideration. In another embodiment, when the complex of the present disclosure is used as a meat substitute, it may be possible to improve the handling of the product while leaving the fibrous texture to achieve a more appropriate texture expression. In another embodiment, when the complex of the present disclosure is used as a material for forming a film, appropriate grinding conditions can be selected to optimize the network formation between the fiber and the water-soluble polysaccharide that should be generated by the disintegration of the water-insoluble carbohydrate. For example, examples of materials for forming a film include edible films, antibacterial coated films (with chitosan), oblate substitutes, biodegradable sheet materials, medical films (artificial skin, etc.), water-absorbent film materials, and functional film materials that are derivatized using functional groups derived from water-soluble polysaccharides as necessary and have water permeability, water repellency, biorecognition, catalytic activity, color tone, fluorescence, cohesion, etc., can be mentioned.

[0043] When disintegrating water-insoluble carbohydrates, a shear force is applied to the water-insoluble carbohydrates to break them into two or more chunks. That is, in the present disclosure, when disintegrating water-insoluble carbohydrates such as bacterial cellulose in which water-insoluble cellulose chains are associated as described above, a substance that interacts with the water-insoluble carbohydrates (e.g., water-soluble polysaccharides) is made to coexist, thereby preventing the inhibition of disintegration due to reassociation between the carbohydrates that constitute the water-insoluble carbohydrates during disintegration, and a disintegrated product can be easily obtained. When carbohydrates that have been disintegrated once reassociate with each other, for example, in bacterial cellulose, it is believed that during disintegration, amorphous carbohydrates are released and the amorphous carbohydrates interact with the hydrophobic surfaces of carbohydrate crystals located at or near the peeled site. The inventors hypothesized that even if amorphous carbohydrates are released, if the hydrophobic surfaces of the crystals are protected by another substance, interactions that lead to reassociation will be less likely to occur. They added a substance that interacts with water-insoluble carbohydrates (e.g., a water-soluble polysaccharide) and confirmed that dissociation was promoted as hypothesized, leading to the present invention.

[0044] As described above, the present invention provides a complex containing a water-soluble polysaccharide and a water-insoluble carbohydrate by covering the hydrophobic surface of new water-insoluble carbohydrates (such as bacterial cellulose) generated during disaggregation with a water-soluble polysaccharide. Therefore, compared with the case where water-soluble polysaccharide dissolved in water is not present during disaggregation of the water-insoluble carbohydrate, the complex of the present disclosure is less likely to cause reassociation between carbohydrates once disaggregated during disaggregation, and as a result, the positions of reassociation are separated or the strength of reassociation is weakened, and the structure of the finally obtained supramolecules (molecules that have a structure held together by covalent bonds and non-covalent bonds) is expanded. The difference in the frequency of such reassociation is the reason why the complex of the present disclosure obtained by causing water-soluble polysaccharide dissolved in water to coexist during disaggregation of the water-insoluble carbohydrate and the composition obtained by mixing the water-soluble polysaccharide after disaggregation of the water-insoluble carbohydrate have the same basic chemical structure (except for the decomposition of the polymer by shearing), and the complex of the present invention is a highly dispersible substance.

[0045] In one embodiment of the present disclosure, whether the complex of the present disclosure is more highly disaggregated than conventional disaggregation means can be confirmed by any means, for example, by comparing the volume of the complex of the present disclosure with a composition in which a water-soluble polysaccharide is mixed after disaggregation of a water-insoluble carbohydrate, since the complex has a larger volume than the composition. In this case, the increased volume can be, for example, about 1.01 times or more, about 1.05 times or more, about 1.1 times or more, about 1.2 times or more, about 1.5 times or more, about 1.7 times or more, about 2.0 times or more, about 2.5 times or more, about 3 times or more, etc.

[0046] In another embodiment, the evaluation of disaggregation can be performed using the permeability of the mesh. For example, when compared with a composition in which a water-soluble polysaccharide is mixed after disaggregation of a water-insoluble carbohydrate, the complex of the present disclosure can increase the amount of the fraction passing through a mesh with a pore size of 500 micrometers. In another embodiment, when a polysaccharide with high water retention is used in producing the complex of the present disclosure, a layer containing a lot of water is formed, making it difficult to pass through the mesh. In this case, the value of the material as a material with high water retention and suitable for film formability can be evaluated by not passing through the mesh.

[0047] In other embodiments, the evaluation of disaggregation can also be performed using the proportion of free water-soluble polysaccharide in the complex. For example, in the complex of the present disclosure, compared to a composition in which a water-soluble polysaccharide is mixed after disaggregation of a water-insoluble carbohydrate, the proportion of free water-soluble polysaccharide can be reduced because the water-soluble polysaccharide can be efficiently incorporated into the complex. For example, in the complex of the present disclosure, compared to a composition in which a water-soluble polysaccharide is mixed after disaggregation of a water-insoluble carbohydrate, the complex can contain less than about 90%, less than about 70%, less than about 50%, less than about 30%, less than about 10%, less than about 5%, less than about 3%, or less than about 1% of free water-soluble polysaccharide.

[0048] This disintegration process induces interactions between water-insoluble carbohydrates and water-soluble polysaccharides to form complexes with new structures, thereby improving the dispersibility of the water-insoluble carbohydrates and imparting moldability, and modifying the water-retention properties to impart binding properties, thickening stability, etc., thereby creating disintegrated products with new material value.

[0049] Conventionally, the disaggregation process of water-insoluble carbohydrates has not been efficient. For example, even when bacterial cellulose gel is disaggregated in water, many lumps remain, and in order to seemingly eliminate these lumps, it is necessary to repeatedly or thoroughly apply shear force using a high-pressure homogenizer or ultrasonic crusher, as shown in previous studies. In this way, by applying a large amount of shear energy, a dispersible disaggregate can finally be obtained, but the range of industrial use of the disaggregate is limited due to issues such as special equipment, processing time, and processing capacity.

[0050] As seen in the formation and persistence of such clumps, the reason why disaggregation does not go well may be that water-insoluble carbohydrates cannot be torn off even when shear force is applied, or that they re-associate after being torn off. Water-insoluble carbohydrates are insoluble in water due to various interactions, the most important of which is the non-covalent association between carbohydrate molecules. Water-insoluble carbohydrates maintain their insoluble structure without showing solubility in water or sufficient hydration or dispersibility due to the strong intermolecular association force. Even if a shear force is applied to this water-insoluble carbohydrate and some of the associated carbohydrate molecules are successfully disaggregated, it is thought that the entire mass will remain untorn due to the binding force of the parts that exist in the disaggregated mass that are about to be torn off and still maintain their associated structure. It is thought that some of the carbohydrate molecules that are temporarily torn off from their associated partners will re-associate with the same or different water-insoluble carbohydrate surfaces, thereby maintaining and regenerating their resistance to shear.

[0051] In this situation, the present inventors have considered that it is important to reduce the possibility of reassociation of water-insoluble carbohydrates after they are partially disaggregated by shear force, thereby separating the disaggregated parts from the space where they are likely to reaggregate, and have arrived at the present invention. Specifically, they have found that disaggregates can be efficiently obtained by allowing a water-soluble polysaccharide that interacts with water-insoluble carbohydrates to coexist in a dissolved state. It was presumed that the dissolved water-soluble polysaccharide interacts with the new carbohydrate surface generated by the water-insoluble carbohydrates being subjected to shear force, forming a complex, thereby suppressing the reassociation of the water-insoluble carbohydrates and allowing time for the clumps to be sufficiently separated from each other.

[0052] Although the water-insoluble carbohydrates are finally converted into an aqueous dispersion by the disintegration step, the aqueous dispersion obtained by the disintegration step in the present invention is considered to be a different material because the reassociation pattern of the water-insoluble carbohydrates is different from that of the aqueous dispersion obtained by the disintegration step in which the water-soluble polysaccharide is not present in a dissolved state. The examples in the present invention also show that the properties of the two materials produced under the same disintegration conditions, such as water dispersibility and the amount of water-soluble polysaccharide adsorption, are different.

[0053] Research on the mixture of bacterial cellulose and water-soluble polysaccharides has been conducted on the technique of improving the properties of the final product by adding water-soluble polysaccharides to the culture medium of the producing bacteria, in particular, or on the model of analyzing the interaction between cellulose and cell wall polysaccharides. However, these studies do not intend to consider the interaction between the cellulose surface and the water-soluble polysaccharide newly generated during disaggregation as described above. In addition, focusing on the interaction between the water-soluble polysaccharide and the solvent, a technique for allowing the cellulose after disaggregation to coexist with the water-soluble polysaccharide and a technique for adding polysaccharides before disaggregation of bacterial cellulose have been proposed. However, these techniques are different from the complex of the present disclosure because they cannot prevent the inhibition of disaggregation due to the reassociation between cellulose and cellulose by the interaction between the cellulose surface newly generated during disaggregation and the water-soluble polysaccharide as described above.

[0054] In one embodiment, the complex of the present disclosure is in the form of a suspension, a sol, or a sol close to a gel, and the state can be controlled by the origin of the water-insoluble carbohydrate, the composition ratio of each component, the characteristics of the water-soluble polysaccharide, the processing conditions, etc. In one embodiment of the present disclosure, the complex of the present disclosure can be prepared as a creamy to fatty substance, and can be used as a fat substitute, a meat substitute, or an emulsion material. Since the complex of the present disclosure is made from a material that is not digested and absorbed in the small intestine, it is zero to low in calories and can also function as dietary fiber. In addition, some polysaccharides, such as (1-3) and (1-4) β-glucan, are expected to have tertiary functionality.

[0055] In one embodiment, when soybean flour or potato flour or the like is kneaded with the complex of the present disclosure (for example, a complex obtained by disintegration in the presence of (1-3) and (1-4) β-glucan), the binding property is superior under high moisture conditions compared to the case of binding with water alone. In addition, powders and granules derived from grains, potatoes, beans, vegetables, fruits, etc., are dried in a state in which part of the cell wall is fragmented and exposed, and highly water-absorbent substances such as pectin, xyloglucan, (1-3) and (1-4) β-glucan are exposed or eluted. The surface of disintegrated water-insoluble carbohydrates, such as cellulose, has a high interaction with these highly water-absorbent substances, and therefore exhibits binding properties to the complex dispersed in water. This is thought to be the cause of the high binding property as well as the physical stabilization of the dispersion of the powder and granules by the complex having a fibrous structure. Compared to the case of mixing soybean flour or potato flour with water, the adhesion during kneading is reduced, and adhesion to containers and utensils can be prevented. As described above, powders and granules derived from grains, potatoes, beans, vegetables, fruits, etc. have a part of the cell wall fragmented and exposed, and are dried in a state in which highly water-absorbent substances such as pectin, xyloglucan, (1-3), (1-4) β-glucan are exposed or dissolved. Therefore, at the water absorption stage, only the powders and granules that come into contact with water expand greatly due to their high absorption power, and water is not easily distributed to the powders and granules that have not yet come into contact with water, resulting in localized water absorption (so-called lumps). This phenomenon is a serious problem that reduces operability and reproducibility not only in normal cooking processes but also during automatic processing in 3D food printers. On the other hand, when the powders and granules are brought into contact with water in a form that allows them to coexist with the composite of the present disclosure, the rate of water movement from the composite, which has a high water retention capacity, to the powders and granules is slowed down, and excessive water absorption of the powders and granules during kneading and stirring is unlikely to occur, which is thought to suppress the development of adhesion and make it difficult for lumps to form. Over time, highly absorbent substances may absorb water and become more viscous; however, if the operating time of a 3D food printer or the like is not particularly long, it is expected that the process of turning powder or granular material into a paste in the presence of the composite of the present disclosure can be made more efficient.In still another embodiment, by kneading the complex of the present disclosure with soy flour or microcrystalline cellulose and heating in an oven, the resulting baked confectionery-like molded product can have a good chewy texture, as opposed to the powdery texture that results when mixed with water instead of the complex of the present disclosure.

[0056] In one embodiment of the present disclosure, the complex of the present disclosure can improve the binding property of the object to be bound, which is believed to occur due to interaction (non-covalent bond) with the components of the complex of the present disclosure. For example, it is believed that the binding property of the object is improved by interacting with plant cell walls, seaweed cell walls, animal tissues, microbial tissues, etc. In another embodiment, when the complex of the present disclosure has a charge (such as when chitosan, alginic acid, or glucuronoxylan is used as a water-soluble polysaccharide), it is believed that the binding property is improved when the mixed object has an opposite charge or when they are bound to each other by electrostatic interaction via ions such as calcium. In another embodiment, the complex of the present disclosure may interact with ionized components and tissues, and since insoluble carbohydrates such as cellulose have a hydrophobic portion, it can also adsorb hydrophobic components. In this way, it can also interact with polar and non-polar components present in the liquid.

[0057] In one embodiment of the present disclosure, the composite of the present disclosure is mixed with a food material to form a material with high binding properties, and then molded and / or dried to obtain a dry solid. For example, a material derived from vegetable powder such as soybeans, potatoes, cabbage, etc., which is processed into a rod shape by mixing the composite of the present disclosure with a food material, can be obtained. In addition to being easy to handle like a solid curry roux, such a dry solid can be used in a desired amount by, for example, cutting it like a pencil sharpener. In addition, a unique texture can be imparted by controlling the shape (thickness, shape, etc.) of the part obtained after cutting. This technology proposes a new shape for the cartridge of a 3D food printer, and for example, a fixed amount of material can be supplied with good reproducibility by automatic operation such as mechanically cutting out a programmed amount of material.

[0058] In one embodiment of the present disclosure, the complex of the present disclosure can suppress the adhesiveness of the object to be mixed. As described above, the adhesiveness of the object to be mixed with the complex of the present disclosure is improved, and the object to be mixed becomes hard, so that the mixture that has improved adhesiveness and become hard does not adhere to other substances for a long time and becomes in a state of reduced adhesiveness.

[0059] In one embodiment, the complex of the present disclosure can change the thickening stability of the object to be mixed. Important functions of the complex of the present disclosure include improved binding and improved dispersibility. In addition, thickening stability can be caused based on improved binding, and it is considered that the interaction between the complex of the present disclosure and the object to be mixed as described above causes the entire complex to harden and increase in viscosity. In addition, when the interaction is low, it is considered that the thickening effect is exhibited by dispersing the object to be mixed or by holding water and reducing the actual water concentration.

[0060] In one embodiment of the present disclosure, the physical properties and characteristics of the complex of the present disclosure can be modified by adding auxiliary materials as necessary. For example, when the complex of the present disclosure is used as a food material or food, seasonings, sugar, starch, fats and oils, proteins, inorganic salts, gelling agents, other foods and their processed products, nutritional components, functional components, and the like can be added. Cellulose is highly compatible with these auxiliary materials, but the compatibility of these materials with polysaccharides or the influence on the interaction between cellulose and polysaccharides that constitute the complex varies depending on the polysaccharide and disintegration conditions, etc., so it is preferable to determine the scope of application individually. For example, the effects of salt and pH can affect the charging effect and the accompanying dispersion effect depending on the polysaccharide, and can control the dispersion state.

[0061] In one embodiment, the shape of the dispersion can be controlled by utilizing the gelling ability of the polysaccharide. For example, a method of preparing a complex of the present disclosure by adding chitosan as a polysaccharide, and then adding the complex to alkaline water to cause gelation, a method of preparing a complex of the present disclosure by adding sodium alginate as a polysaccharide, and then adding the complex to water containing calcium ions to cause gelation, and the like can be mentioned. In one embodiment, a gel with high homogeneity can be formed by mixing a particulate gelling agent before gelation, such as agar particles or curdlan particles, with the complex of the present disclosure, dispersing the mixture in water, and then subjecting the mixture to a heating treatment or a heating and cooling treatment. Therefore, in one embodiment, a gel with high homogeneity can be formed by a method including a step of disintegrating a water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water, a step of mixing a complex containing the water-soluble polysaccharide and the water-insoluble carbohydrate obtained by the disintegrating step with a gelling agent to obtain a mixture, a step of dispersing the mixture in a solvent, and a step of subjecting the mixture to a heating and / or cooling treatment.

[0062] In one embodiment, the heat treatment may include laser processing. Laser processing can be performed using equipment well known in the art, and the structure of the irradiated part or its surroundings can be directly or indirectly modified by applying light to a part of the object and heating the periphery of the irradiated part or inducing a photochemical reaction. For structural modification of food, for example, blue laser light can be used. When using blue laser light, it is important that the irradiated part is appropriately colored, since it is necessary for the irradiated part to absorb the light. For coloring, for example, the following food materials can be used, but it is also possible to use the color tone obtained by heating, seasoning, or coloring food, or the colored parts of agricultural products, and the like, and the coloring is not limited to these. Examples of red materials: paprika, chili pepper, purple onion, purple potato, carrot, tomato, beet, strawberry, cherry blossom, watermelon, blueberry Examples of green ingredients: spinach, komatsuna, chrysanthemum, cabbage, broccoli, bell peppers, kale, shiso leaves, matcha, edamame, parsley, basil Examples of yellow / brown ingredients: yellow pepper, turmeric, pumpkin, lemon, mandarin orange, yuzu, mango, pineapple, coriander, cumin

[0063] In one embodiment, the complex of the present disclosure enables the dispersion of water-insoluble particles with a specific gravity higher than water that coexist during the formation of a food gel. Examples of water-insoluble particles with a specific gravity higher than water include, for example, vegetable powders derived from grains, beans, vegetables, fruits, etc., powders derived from animals and seafood, powders derived from microorganisms, and powders derived from processed products of these food materials. In addition, food gels include calcium alginate gel, pectin gel, agar gel, carrageenan gel, gelatin gel, starch gel, curdlan gel, etc. Before the materials constituting these gels solidify, water-insoluble particles with a specific gravity higher than water are added to solidify the gel. However, since most of these water-insoluble particles settle before the gel solidifies, in order to disperse them homogeneously, it is time-consuming to carefully disperse them while stirring just before solidification. In addition, before gelation, thickening stabilizers such as xanthan gum and specific gravity adjusters such as sugar can be added to suppress sedimentation, but this affects the texture and taste. By allowing the complex of the present disclosure to coexist, the sedimentation rate is reduced and the dispersibility is improved due to the interaction between the complex and water-insoluble particles having a higher specific gravity than water or physical trapping. Therefore, in one embodiment, a food or drink containing the complex of the present disclosure and a gelling agent can be provided, and the complex of the present disclosure and the gelling agent may be mixed and then laser processed to form the food or drink, or the gelling agent or droplets may be placed on the complex of the present disclosure after laser processing.

[0064] In one embodiment, the complex of the present disclosure can be mixed with food powder, dispersed, and given the desired physical properties to prepare a soft food with a good mouthfeel. For example, by mixing nata puree (the complex of the present disclosure using desugared nata de coco as a raw material) with grain flour, dispersing the grain flour, and heating the dispersed grain flour to form a material in which the grain flour is modified into a paste, it is possible to give the material properties of liquid porridge to self-supporting whipped cream. This material can be a food that places less strain on people who have difficulty chewing or swallowing. By dispersing low-concentration powder using the technology of the present disclosure, the food preparation process is simplified and the suitability for automatic cooking processes is improved. In addition, in one embodiment of the present disclosure, the complex of the present disclosure can be used to provide a material with whipped cream-like physical properties, which gives the material value as a fat or oil substitute or a lipid substitute and can be used in the preparation and processing of foods such as confectionery.

[0065] In one embodiment, it is also possible to provide a food material in a form similar to a gel by adjusting the preparation method of the complex of the present disclosure and the ingredients mixed therein. For example, by using the complex of the present disclosure prepared using a high concentration of tamarind seed gum aqueous solution, a sol-like material with relatively low fluidity similar to a gel can be provided, and this property is further improved by adding guar gum. These materials have less viscosity than those found in high concentration thickening stabilizers and exhibit good mouthfeel properties. Furthermore, in another embodiment, the complex of the present disclosure (e.g., nata puree) and starch-based powder such as grain flour are mixed, and the powder is dispersed, and heated directly or after appropriate preheating or addition of materials such as gelling agents and colorants to reduce moisture, thereby forming a sheet-like or granular semi-dried or dried material.

[0066] In one embodiment, the composite of the present disclosure can be heated, cooled, dried, etc., after mixing with auxiliary materials as necessary. Except for special cases such as scorching, there is little change in the chemical structure of cellulose during food production under normal conditions. The polysaccharide to be added is affected by pH and temperature, and may also be affected by enzymes derived from coexisting fresh ingredients. Some materials can be formed into structures such as films and fibers by drying, and can be powdered after drying. The dried material has high storage stability, and by selecting conditions according to the material, it can be added with water to restore the shape partially or completely to form a dispersion. Furthermore, it can be applied as a biocompatible material, biodegradable material, etc. For example, as a biodegradable material or biocompatible material, it can be used as a filler during biocomposite production, and when making paper, in addition to affinity with cellulose fibers, formability that does not shrink or become unevenly distributed is also important, and the film formability of the composite of the present disclosure is useful.

[0067] Among the complexes of the present disclosure, for example, a disaggregate (complex) obtained by selecting cellulose as the insoluble carbohydrate and (1-3) or (1-4) β-glucan as the water-soluble polysaccharide not only exhibits good film formability, but also forms a film having a water permeability suppressing function after drying. Since the complex is obtained in a state of being suspended in water, it can be contacted with a structure whose surface is to be covered with a film by an operation such as coating, spraying, or immersion, and then dried to form a coating with low water permeability on the surface of the structure. By forming this coating, when the structure is allowed to absorb water, it is possible to suppress the penetration of water from the surface of the structure and slow down the rate of change in the physical properties of the structure. This action allows a composition to be prepared in which a suspension of the disaggregate is impregnated into the inside of a soft sponge-like structure, and then the structure is dried to form a film having a water permeability suppressing function. When this composition is allowed to absorb water, the presence of the film changes the water absorption characteristics inside, which makes it possible to delay the change in the physical properties inside and impart hardness and a unique texture. This method can be applied to modify the properties of structures derived from chopped or crushed fruits and vegetables.

[0068] Therefore, in one embodiment of the present disclosure, a water permeation suppression or control agent containing the complex of the present disclosure can be provided. The complex of the present disclosure can be used as a coating to control the change in the physical properties of the internal substance, and the state of the internal substance may be any form, such as powder or liquid. For example, if the internal substance is liquid, the complex of the present disclosure can be used as a membrane to hold the liquid inside. This makes it possible to embed droplets filled with flavors and aromas, or stably embed juicy sauces inside to release liquid when chewed, when designing new foods such as 3D printed foods. It is also possible to place a membrane, create small checkerboard-shaped partitions on top of it, and place drops of different colors and flavors in each square.

[0069] In another embodiment, when designing a new food such as a 3D printed food using the composite of the present disclosure as a membrane, ingredients such as vegetables can be rolled up like fresh spring rolls. In this case, it is possible to suppress the diffusion of the internal material. In addition, by hardening the membrane, it is possible to create a texture similar to the burnt texture of stone-grilled bibimbap, and since the composite of the present disclosure has low water permeability, it is possible to prevent the burnt ingredients from suddenly absorbing the surrounding water and softening.

[0070] When the complex of the present disclosure is used as a membrane to hold a liquid inside, the membrane of the complex of the present disclosure will be present at the liquid-liquid interface, and it is also possible to slow down the diffusion rate. In one embodiment, when the membrane of the complex of the present disclosure is charged, it can also be made into an ion-selective membrane. For example, when an aqueous solution containing dissolved calcium ions is placed on one side separated by the membrane of the complex of the present disclosure and an aqueous solution containing dissolved alginic acid is placed on the other side, both will gel near the membrane to form a thin membrane. When a gel membrane is formed, the water permeability is further reduced, so that the liquid on both sides can be stably held, and it is also possible to release the liquid only from the part that is not double-coated.

[0071] In another embodiment, when a suspension in which fine particles are dispersed in the composite of the present disclosure is formed into a membrane, the membrane is blocked, and the water permeability is reduced. Therefore, by placing a suspension of fine particles on one side of the membrane of the composite of the present disclosure, the water permeability of the membrane can be reduced. In another embodiment, the water absorption characteristics can be changed by contacting a powder with the membrane of the composite of the present disclosure, or the water permeability of the liquid can be reduced by placing a gas (void) at the interface of the membrane of the composite of the present disclosure.

[0072] In one embodiment, the composite of the present disclosure can be used as a guide for property modification based on whether or not non-uniform fiber dispersion is visible when water is added and dispersed as necessary, or the degree of the non-uniform fiber dispersion. After the composite of the present disclosure is dispersed by adding water as necessary, it can be evaluated by passing it through a screen with a mesh of about 0.5 mm and measuring the difference in turbidity (for example, the transmittance of light at 600 nm) before and after passing through. Composites with good permeability and granular with high dispersibility are highly useful as cream or emulsion materials. On the other hand, there are also composites with low permeability that have a high degree of fiber dispersion, and in such samples, the filtration rate is significantly reduced, but the cellulose and polysaccharide form a network and have value as a material with film-forming properties. Such samples can also be subjected to film-forming and drying processes. In this way, the composite of the present disclosure has high adaptability to various substances and processes, and has reduced adhesion to utensils, making it important as a material in automatic cooking processes, especially 3D food printers. In one embodiment, when the complex of the present disclosure is made into a cream-like substance, it becomes easy to handle, and the biodegradation characteristics, bioaffinity and biofunctionality (compatibility and interactivity) can be changed depending on the properties of the water-soluble polysaccharide. For example, a cream containing chitosan can be made to have antibacterial properties. Therefore, in one embodiment, a mixture of the complex of the present disclosure and a food or drink can be used as a food or drink (material or ingredient) that can be used for processing in a 3D food printer. Such a food or drink for a 3D food printer can be produced by a method including a step of disintegrating a water-insoluble carbohydrate in the presence of a water-soluble polysaccharide dissolved in water, and a step of mixing the complex containing the water-soluble polysaccharide and the water-insoluble carbohydrate obtained by the disintegration step with any raw material for the food or drink.

[0073] In one embodiment, the complex of the present disclosure can be made highly functional by glycoengineering technology. Polysaccharides can be decomposed and modified by enzymatic or chemical methods. For example, polysaccharides can be decomposed to reduce interactions, thereby controlling the structure of the network and leading to modification of physical properties, or polysaccharides can be relinked by the action of glycosyltransferases, or functional groups can be introduced. In addition, positive or negative charges in an aqueous solution can be used to promote new interactions with other substances, or functional groups such as hydroxyl groups, carboxyl groups, and amino groups on the polysaccharide can be modified to impart new functions or construct a network structure. Furthermore, new functional materials can be produced by interactions with other carbohydrates, proteins, lipids, etc. that recognize the molecular structure or higher-order structure of the main chain or side chain of the polysaccharide.

[0074] In one embodiment, the composite of the present disclosure can be prepared by disintegrating in a manner suitable for the manufacturing process of cellulose nanofibers, lignocellulose nanofibers, or chitin nanofibers. In the preparation process of these nanofibers, wet grinding is performed using a wet grinder, bead mill, ball mill, or the like. For example, a composite can be prepared by adding a sample whose fiber structure has been modified by the RURAL process (see Example 28 below) for processing herbaceous fiber such as rice straw as a water-insoluble carbohydrate, (1-3) and (1-4) β-glucan as a water-soluble polysaccharide together with water, and wet grinding using a ball mill. This composite can be made into a nonwoven fabric-like or straw paper-like sheet, for example, by drying the fraction retained on the mesh. By using this sheet, it is possible to manufacture plastic substitute products such as biodegradable disposable tableware and food packaging containers.

[0075] In one embodiment, the complex of the present disclosure can be kneaded with water-insoluble particles such as water-insoluble carbohydrates that have not been subjected to a complexing treatment to bind the water-insoluble particles, and then dried to form a high-density block composition. This composition is expected to have value as a material with low scattering and high operability, a material with high density and high stability during storage, and a material with high operability when measured out, similar to the value of block-shaped curry roux compared to curry powder and curry paste, for example.

[0076] An example of the composition according to the present embodiment is a high-density composition composed of glucan alone. In this case, water-insoluble glucans such as starch, cellulose, and β-1,3-glucan can be used as examples of water-insoluble particles such as water-insoluble carbohydrates that have not been subjected to complex treatment. In addition, as a complex to be bound, for example, a disintegrant using bacterial cellulose as the water-insoluble carbohydrate and (1-3) and (1-4) β-glucan as the water-soluble polysaccharide can be mentioned. After kneading these to bind the water-insoluble particles, the composition according to the present embodiment can be obtained by drying at normal pressure or reduced pressure at a temperature at which the water-insoluble particles can be inhibited from absorbing water and undergoing irreversible changes, for example, when starch is used, at a temperature lower than its gelatinization initiation temperature. During binding or drying, a clay-like hydrated material is handled, and at this time, it can be molded into a desired shape. When molding, it is necessary to consider shrinkage and cracking during drying.

[0077] Water-insoluble particles are partially exposed on the surface of the composition according to the present embodiment, which may cause gradual peeling, water absorption from the surface, or disintegration in water in a short time. In order to prevent this, the complex of the present disclosure may be applied to the surface and dried to reduce water permeability. As a complex for controlling this water permeability, a disintegrant using (1-3) or (1-4) β-glucan as the water-soluble polysaccharide is effective. This surface treatment makes it possible to produce a high-density composition composed only of edible glucan, which has reduced disintegration and water permeability. This composition provides a new method for controlling the circulation of organic carbon resources and food resources as a sugar mass with excellent storage properties.

[0078] Furthermore, the compositions with controlled water permeability obtained by these methods can exhibit the functions of the water-insoluble particles according to the degree of water permeability, such as the gelatinization and disintegration of starch, the sustained release of functional ingredients and nutrients, and the physical disintegration of the composition. EXAMPLES

[0079] (Example 1: Formation of disintegrated products from various celluloses in the presence of polysaccharides (1)) In this example, it was confirmed whether or not various cellulose disintegrates were produced in the presence of polysaccharides. The details are shown below.

[0080] Methods and Materials Desugaring method for bacterial cellulose (BC, domestically produced Nata de Coco (for commercial use), Fujicco Co., Ltd.). 3 kg of commercial Nata de Coco was placed in a 20 L container, 15 L of tap water was added, and gently stirred. Desugaring was performed by changing the water every 24 hours for a total of 5 times. 100 g of the desugared solid content (0.5%) was taken as a wet weight, and 40 mL of 0.7% polysaccharide solution was added, and the mixture was disintegrated by grinding in a household (food) mixer (Power Blender SPB-650J, Conair Japan LLC) at a speed of 15,000 rpm for 30 seconds x 4 times. The 0.7% polysaccharide solution was prepared by adding a predetermined amount of polysaccharide little by little while suspending the water with a magnetic stirrer. Since xyloglucan was not fully dissolved at this time, it was completely dissolved by heating in a microwave oven. Then, a part of the disintegrated product (5 g) was diluted 8 times with 35 mL of ion-exchanged water. The liquid was passed through a 0.5 mm mesh screen. [Table 1]

[0081] (result) As a result, the sample ground in the presence of polysaccharides showed different characteristics from the sample ground using only desugared BC. In addition, the turbidity at 600 nm was measured for the 8-fold diluted sample and the filtrate after the screen pass, and the screen transmittance (%) was calculated by taking the ratio (Figure 1A).

[0082] Thus, the fraction passing through the screen increased dramatically in the pulp containing each polysaccharide. This is thought to be due to the suppression of entanglement of cellulose fibers, resulting in finer particles.

[0083] Next, 100 g of bacterial cellulose (BC, Morinaga & Co., Ltd.) (solid content 0.68%) desugared using the above method was taken, and 40 mL of SQ water or 0.7% polysaccharide solution (xyloglucan, (1-3), (1-4) β-glucan or xanthan gum) was added, and then the mixture was ground in a household (food) mixer (Power Blender SPB-650J, Conair Japan LLC) at a speed of 15,000 rpm for 30 seconds x 4 times. The 0.7% polysaccharide solution was prepared by the method of Example 1. 20 g of the resulting sol-like BC crushed material was placed in a 50 mL plastic tube, 5.7 mL of SQ water was added, and the mixture was shaken back and forth (150 rpm) at room temperature for 1 hour. As a control, 20 g of BC crushed material ground with 40 mL of SQ water was placed in a 50 mL plastic tube, and a polysaccharide solution corresponding to each test group was added to make the polysaccharide concentration the same as that of the test group, and the mixture was shaken in the same manner. SQ water was then added to each plastic tube to bring the total volume to 45 mL, and the tubes were centrifuged at 3,500 rpm, 4°C, and 10 minutes using a high-speed refrigerated centrifuge (Suprema25, TOMY) and a swing rotor (TS-36N). The apparent volume of the BC fragments precipitated after centrifugation was measured.

[0084] As a result, the values ​​shown in the table below were obtained. [Table 2]

[0085] Compared to the sample where polysaccharide was added after maceration (control group), the sample where polysaccharide was added before maceration (test group) was dispersed 1.7 to 1.8 times. Thus, it was found that the properties of the resulting BC maceration differ depending on the timing of adding polysaccharide during the maceration process, and that adding polysaccharide during maceration can produce a material with unique properties.

[0086] Next, a portion of the supernatant from the control group (BC + xyloglucan (added after disaggregation)) and the test group (BC + xyloglucan (added before disaggregation)) was collected, and the glucose concentration after sulfuric acid hydrolysis was measured to estimate the xyloglucan concentration (J. Appl. Glycosci., 66, 11-19 (2019)). It was assumed that all glucose residues derived from cellulose were present in the precipitate. As a result, in the control group, 23% of the added xyloglucan was in a free state, while in the test group, only 3% was in a free state, indicating that the component composition is different. This indicates that the latter processing conditions produce BC fragments that more efficiently incorporate xyloglucan.

[0087] (Example 2: Formation of disintegrated products from various celluloses in the presence of polysaccharides (2)) In this example, similar to Example 1, a different polysaccharide was used and the same test was carried out. Methods and Materials Barley-derived (1-3) and (1-4) β-glucans were dispersed in water and then dissolved by heating in a microwave oven as described in Example 1. Chitosan was dissolved in a hydrochloric acid solution (pH 2.0) instead of water as described in Example 1. Alginic acid was dispersed and dissolved in water as described in Example 1 before use. [Table 3]

[0088] (result) As a result, the sample ground in the presence of polysaccharides showed different properties compared to the sample ground using only desugared BC. It is believed that the formation of a network between cellulose and polysaccharides improved water retention and reduced water permeability, and gel-like properties were observed.

[0089] (Example 3: Application of the macerated material: fat) In this example, an application example of the disaggregate of the present disclosure is shown. (material and method) A portion of the β-glucan-added and disintegrated material from Example 2 was dispensed and centrifuged (18,900 g, 3 minutes, room temperature), after which the supernatant was removed and the sol fraction was collected, to which a few drops of purple sweet potato color (acidic ethanol extract) and carrot color (ethanol extract) were added to obtain a ground chicken sample (Figure 2, left). This was transferred onto a cooking iron plate covered with canola oil, and a few drops of soy sauce were added and cooked for about 1 minute.

[0090] (result) The obtained sample (Figure 2, right) had a texture similar to that of fatty meat, and when pressed with the tongue, it dispersed like fatty meat.

[0091] (Example 4: Application of the macerated product: cookie-like food) In this example, an application example of the disaggregate of the present disclosure is shown. (material and method) 5 g of soy flour (Mitake Foods Co., Ltd.) was mixed with 6 mL of ion-exchanged water (control sample) or 6.0 mL of the β-glucan-added / disintegrated product of Example 2 using a spoon, and each was mixed with 2 g of microcrystalline cellulose (Asahi Kasei Corp., CEOLUS FD-101) and 4 mL of ion-exchanged water that had been previously mixed using a spoon. In this case, the mixture adhered to the spoon and walls in the control sample, whereas there was less adhesion (stickiness) in the sample containing the β-glucan-added / disintegrated product.

[0092] This was then manually shaped into cylindrical cookies measuring 2 cm in diameter and 7 mm in height, and heated in an oven toaster (vertical oven toaster KDTO-001, Lyson Co., Ltd.) at 250 W (top heater only, distance to table 6 cm) for 5 minutes.

[0093] (result) When the chewiness of the obtained samples (Figure 4) was examined, the control sample crumbled into powder when chewed, whereas the sample containing added β-glucan and disintegrated material had elasticity when chewed and the crumbling into powder was suppressed.

[0094] (Example 5: Application of disaggregate: thin film) In this example, an example of the production of a thin film using the disaggregate of the present disclosure is provided. (material and method) Using the β-glucan-added / disintegrated material and the chitosan-added / disintegrated material of Example 2, 8-fold diluted solutions prepared according to the method of Example 1 were poured into the top of a nylon net with a mesh of 0.5 mm, and the non-passing fraction was retained. These were dried at 60°C to obtain thin films of each.

[0095] (result) The results are shown in Figure 5. The semicircle on the left side of each figure is the nylon screen used for membrane production, and the half circle on the right side is the membrane peeled off from it. When a water droplet was placed on the dry thin film produced using (1-3) and (1-4) β-glucan, the water droplet remained on the film, but when placed on the dry thin film produced using chitosan, the water droplet was immediately absorbed into the film. In addition, when the same concentration of (1-3) and (1-4) β-glucan aqueous solutions were placed on a nylon net, almost none of them were retained on the net and fell off, so this film-forming property is considered to be a characteristic of the complex. From this, it can be seen that the membrane of the complex produced by the method of the present disclosure with bacterial cellulose and (1-3) and (1-4) β-glucan has extremely low water absorption.

[0096] Thus, it was possible to form a thin film in the same manner as in the papermaking process without excessive shrinkage during drying. This film is composed of a complex containing water-soluble polysaccharides, and by binding water-soluble polysaccharides, which are highly interactive, to cellulose, which has a relatively low selectivity for interaction, it is possible to effectively present substances with interactive activity. (1-3), (1-4) Materials with β-glucan presented can be used as edible materials to manufacture a variety of processed foods. In addition, chitosan is known to have antibacterial properties, and it is expected to function as an antibacterial film in food sheets, etc. Chitosan has highly chemically reactive amino groups on its surface, which makes it possible to capture and measure metal salts that show interactivity, to derivatize them with color-developing and fluorescent substances by chemical modification, and to create highly functional materials through the presentation of proteins, etc.

[0097] (Example 6: Application of the disintegrated material: noodles) In this example, an example of producing noodles using the macerated material of the present disclosure is provided. (material and method) A portion of the chitosan-added disintegrated material from Example 2 was filled into a 10 mL plastic syringe and extruded dropwise at a rate of 5 mL per minute into 0.01 M sodium hydroxide aqueous solution (100 mL) stirred with a magnetic stirrer. As a result, the disintegrated material gelled into noodles in the liquid. In addition, 3 g of the sodium alginate-added disintegrated material was mixed with rice starch (Motyl B, Joetsu Starch Co., Ltd.), and extruded dropwise at a rate of 5 mL per minute into 200 mM calcium chloride aqueous solution (100 mL) stirred with a magnetic stirrer.

[0098] (result) As a result, as shown in FIG. 6, the mixture of the disintegrated material and starch gelled in the liquid into white noodles.

[0099] From the above, in addition to producing gelled foods with texture, it will be possible to produce bead-shaped molded products containing functional substances, expanding the functions of edible and non-edible products. As shown in Example 26 below, it is also expected to have a stabilizing effect on the complex, such as maintaining the dispersibility of powder in agar gel. It will be a means of expressing various textures with 3D food printers, preserving nutrients, functional ingredients, taste and aroma ingredients, and controlling scattering.

[0100] (Example 7: Application of disintegrated material: Effect of inactivation procedure) In this example, the effect of inactivating enzymes on the disaggregates of the present disclosure was observed. (material and method) 0.75 mL of the β-glucan-added / disintegrated material from Example 2 was placed in a tube, diluted twice with ion-exchanged water, and inverted upside down to disperse the sol. Two tubes were then prepared. Then, 0.005 mL of Lichenase (Magazyme, E-LiCHN, Lot60101a) was added to 0.1 mL of ion-exchanged water. One was inactivated by incubating it in a heat block at 100℃ for 10 minutes. 0.075mL of each lichenase solution was added to the tube containing the dispersion of the β-glucan-added / disintegrated product. This was reacted at 60℃.

[0101] (result) As a result, no change was observed in the group that had received the inactivated enzyme, but in the group that received the uninactivated lichenase, a decrease in turbidity and an improvement in fluidity were observed after three minutes.

[0102] (Example 8: Application of disintegrated material: soy sauce) In this example, an example of producing a soy sauce sauce using the disaggregate of the present disclosure is shown. (material and method) 1 mL of the xyloglucan-added disintegrated material from Example 1 was placed in a tube and centrifuged (18,900 g, 3 minutes, room temperature), after which the supernatant was removed to recover the sol fraction, which was then mixed with 0.6 mL of soy sauce to prepare a thick soy sauce sauce.

[0103] (result) The results are shown in Figure 7.

[0104] In this way, by mixing a water-soluble liquid seasoning with the complex, a sol-like food with reduced fluidity can be provided. It is expected that not only will it prevent the contents from scattering during transportation of ready-meal products, but it will also have the effects of providing stability during ejection during automatic operation with a 3D food printer, stability during application, prevention of drying in a thin layer, and prevention of component migration due to the hydrophilic or hydrophobic layer. It is also expected to be used in skin protection creams, rinses, abrasives, disinfectants, etc.

[0105] (Example 9: Application of disintegrated material: String-like and spiral-like material that can be used for 3D food printers, etc.) In this example, an example of generating string-like and spiral-like objects that can be used in 3D food printers and the like using the disaggregated material of the present disclosure is shown. (material and method) 9mL of sodium alginate-added BC disintegrated in Example 2 (Suspension A) and 9mL of xyloglucan-added BC disintegrated in Example 1 with 0.225mL of 4M CaCl2 (Suspension B) were filled into 10mL syringes, set in a constant-speed liquid delivery device (PicoPlus, Harvard Apparatus), and extruded simultaneously at 0.5mL / min, designed to be mixed after extrusion and extruded to the outside by joining the three-way flow path. 8mm from mixing to ejection. Figure 8 shows a schematic diagram of the syringe installation style used (left) and a photograph after installation (right).

[0106] (result) The results are shown in Figures 9 and 10. As a result, mixing of suspension A and suspension B occurred within the flow path, and a string-like gel was confirmed in the SQ water in the petri dish for receiving the ejected material (Figure 9), as shown in the photograph in Figure 8 (right).

[0107] Next, potato starch (1.5 g) was added to suspension B (4 mL) and mixed thoroughly, then filled into a syringe (suspension C), which was then replaced with the syringe containing suspension B in the same manner as in the above test, and extruded simultaneously with suspension A to form a gel containing starch into a platform shape. This was then lifted by hand, placed on cooking paper, and heated for 5 minutes in a toaster oven (vertical toaster oven KDTO-001, Lyson Co., Ltd.) at 250 W (top heater only, distance to platform 6 cm) to gelatinize the starch, resulting in a molded product that was thick but not sticky and could be lifted by hand (Figure 10). When biting into this, it was slightly elastic but easy to bite through.

[0108] (Example 10: Application of disintegrated material: gummy material) In this example, an example of producing a gummy material using the disintegrated material of the present disclosure is shown. (material and method) 4 g of rice starch (Fine Snow, Joetsu Starch) was added to 6 mL of the BC β-glucan-added / disintegrated product of Example 2, and the mixture was then kneaded and filled into a 10 mL syringe. The contents were then ejected from the syringe at 3 mL / min to form a molded product on the side of a plate with a diameter of 15 cm. After that, 1 mL of SQ water was dropped into the center of the plate so as not to come into contact with the molded product, and the entire top was covered with food packaging wrap film (Saran Wrap, Asahi Kasei Home Products Co., Ltd.) and steam-heated in a microwave oven (EM-A20(W), Sanyo Electric Co., Ltd.) at 500 W for 2 minutes.

[0109] (result) The results are shown in Figures 11 to 13. As a result of the above, the molded products were hard and crunchy on the outside and many were hard on the inside as well, but those molded into granules about 5 mm in diameter had a gummy-like elasticity on the inside.

[0110] In addition, when rice starch was mixed with the same amount of SQ water instead of the BC β-glucan-added and disintegrated product in Example 2, a liquid suspension with low viscosity and high fluidity was formed, and it could not be molded under these conditions.

[0111] (Example 11: Application of the macerated product: Hamburger steak) In this example, an example of the production of a hamburger using the pulverized product of the present disclosure is shown. (material and method) 4 g of meat substitute food (veggie mince made from soybeans and brown rice, Meissen Fine Food Co., Ltd.) was crushed in a mortar for 5 minutes to turn the cylindrical parts into granules with a diameter of 2 mm or less, and then 6 mL of SQ water or 6 mL of the BC β-glucan-added / disintegrated product from Example 2 was added and kneaded with a spatula. The sample to which SQ water was added did not bind and remained in a crumbly state, but the sample to which BC β-glucan-added / disintegrated product was added bound and could be molded.

[0112] This molded product is used as a hamburger-like food in a toaster oven (vertical toaster oven The plates were heated for a total of 10 minutes using a KDTO-001 (Ryson Co., Ltd.) at 250 W (upper heater only, distance to table 6 cm) for 5 minutes on each side.

[0113] (result) The results are shown in Figures 14 and 15. As a result, no separation of the grains was observed during heating, and they remained bonded together. In addition, when chewed, they did not become crumbly, but remained chewy.

[0114] (Example 12: Application of the pulverized material: confectionery) In this example, an example of producing confectionery using the disintegrated material of the present disclosure is shown. (material and method) 2 g of each of the vegetable powders (purple sweet potato, pumpkin, spinach, spinach / rice starch (fine snow) = 3:1) were weighed out and mixed with 3 mL of the β-glucan-added and disintegrated product of BC in Example 2, and kneaded to form a paste (powder order: (1) to (4)). Then, (1) and (2) were molded into cylindrical shapes with a diameter of 8 mm and a height of 3 mm, and (3) and (4) were molded into leaf shapes with a major axis of 16 to 20 mm, a minor axis of 8 to 12 mm, and a height of 2 mm, and the molded products were placed on the side of a plate with a diameter of 15 cm, with four pieces spaced apart. Then, 1 mL of SQ water was dropped into the center of the plate so as not to come into contact with the molded products, and the entire top was covered with a food packaging wrap film (Saran Wrap, Asahi Kasei Home Products Co., Ltd.), and steamed and heated in a microwave oven (EM-A20 (W), Sanyo Electric Co., Ltd.) at 500 W for 2 minutes.

[0115] (result) The results will be explained with reference to FIGS. As a result of the above, (1) expanded 1.5 times in the center, was crisp on the outside, and had a firm elasticity like dried sweet potato or chewing gum on the inside. (2) expanded twice in the center, was crunchy and pastry-like on the outside, and had a slightly elasticity like dried persimmon on the inside. (3) did not expand in the height direction, but contracted lengthwise and widthwise, turning a dark green color. It had a burnt chewy texture. (4) did not shrink lengthwise and expanded 1.5-2 times in the lengthwise direction. It became nearly black in color and had a crunchy texture like thin rice crackers.

[0116] (Example 13: Application of disintegrated material: Effects of various sugars) In this example, the effect of various sugars using the disaggregates of the present disclosure is shown. (material and method) The desugaring of BC (Nata de Coco Plain, Morinaga Milk Industry Co., Ltd.) was carried out in the same manner as in Example 1. The solid content of the resulting desugared product was 0.68%. 100 g of this product was taken as a wet weight, and 40 mL of 0.7% polysaccharide solution (dispersed in water and dissolved in the manner of Example 1. κ-carrageenan was dispersed and then dissolved by heating in a microwave oven) was added, followed by disintegration by grinding in a household mixer (Power Blender SPB-650J, Conair Japan LLC) at a speed of 15,000 rpm for 30 seconds x 4 times. Then, a portion of the disintegrated product (5 g) was diluted 8 times with 35 mL of ion-exchanged water. The liquid was passed through a 0.5 mm mesh screen. [Table 4]

[0117] (result) As a result, the samples milled in the presence of polysaccharides showed different characteristics than those using only desugared BC.

[0118] Barley extract was prepared by drying waxy barley (waxy barley, Hakubaku Co., Ltd.) for 12 hours at 70°C, pulverizing it (2 mm screen mesh pass) with a cutter mill grinder (MF 10.1 cutter head, IKA Japan KK), adding 90 mL of water at 40°C to 30 g of the dried barley, shaking it for 1 hour (180 rpm), centrifuging it (23,000 xg, 5 minutes, room temperature), and using 40 mL of the supernatant. The amount of (1-3) and (1-4) β-glucan in the supernatant was measured using a (1-3) and (1-4) β-glucan measurement kit (Megazyme Co., Ltd.) and found to be 0.8%.

[0119] As shown in Table 3, when desugared BC was disaggregated using barley extract that had been treated with lichenase before being added, a disaggregate containing insufficiently disaggregated portions was obtained. This demonstrated that (1-3) and (1-4) β-glucans are among the main components in barley extract that contribute to promoting disaggregation.

[0120] (Example 14 Application of the pulp: meat substitute) This example illustrates the production of meat substitutes utilizing the macerated material of the present disclosure. (material and method) The meat substitute food of Example 11 was prepared using the β-glucan-added / disintegrated product obtained from BC of Example 13, and it was confirmed that a similar procedure was possible.

[0121] (result) The results are shown in Figure 18.

[0122] (Example 15: Application of the pulp: Whipped cream-like food) This example illustrates the production of a whipped cream-like food product utilizing the pulp of the present disclosure.

[0123] (material and method) The BC β-glucan-added disintegrate (100 mL) from Example 2 was centrifuged (25,000 g, 10 min, 4°C) to recover the precipitate, and 32 g of the mixture to which erythritol had been added (final concentration 6% (w / V)) was taken and transferred to a bowl. 40 mL of Whipped Light Melt in the Mouth (Snow Brand Megmilk, vegetable fat 30%) was added to the bowl and stirred with a whisk for 2 minutes to create a foam (Figure 19, left). A portion of this was taken out, extruded from a star-shaped whipped cream extrusion nozzle, and placed on a black plate (Figure 19, right).

[0124] (result) Even when half of the mixture was replaced with a complex derived from low-calorie dietary fiber, a creamy structure could be formed, and sweetening with a non-calorie sweetener was also possible. Thus, the application of this disintegrant is expected to expand the possibilities for cooking and manufacturing calorie-restricted sweets.

[0125] (Example 16: Application of disintegrated material: Floating of lumpy crushed material) In this embodiment, the situation regarding the floating of lump-like ground material of the disintegrated material of the present disclosure was analyzed. (material and method) Following the method of Example 13, 40 mL of 0.7% (w / v) polysaccharide solution (polysaccharide: β-glucan, derived from barley) was added to 100 g wet weight of desugared BC and ground in a mixer for a short period of time (5 to 30 seconds).

[0126] (result) It was confirmed that the amount of floating lumpy ground material was reduced by increasing the grinding time. In this way, it was found that it is possible to control the shape of the fibrous material in the ground material by changing the grinding conditions, and it is possible to flexibly respond to conditions where the fibrous texture is desired to be preserved.

[0127] (Example 17: Application of the disintegrated material: noodle-like food) In this example, an example of producing a noodle-like food product using the macerated material of the present disclosure is shown. (material and method) 6 g of rice starch (Fine Snow, Joetsu Starch) was added to 6 mL of BC β-glucan-added / disintegrated product prepared by the method of Example 2 and kneaded, then the mixture was covered with plastic wrap for 30 minutes to prevent drying, and then filled into a 10 mL syringe used for 3D food printers, etc. Next, the contents were ejected from the syringe at 3 mL / min and added to a pot containing 1 L of boiling water (boiling state, IH pot kettle "Kotor" TOM-17, CB Japan Co., Ltd.). After 1 minute, the contents were collected in a colander and washed with cold water.

[0128] (result) The results are shown in Figures 21 and 22. As a result of this process, semi-transparent noodles of about 10 cm were obtained, which had a chewy elasticity when biting into the noodles and a smooth texture when sliding through the mouth. They did not fall apart when placed in the mouth, but could be easily bitten into.

[0129] The sample was drawn from the syringe into pellets about 5-8 mm high on a plate and air-dried at room temperature for about 10 minutes. It was then added to 1 L of boiling water and treated for 2 minutes. It was then collected and cooled and washed in the same manner as above. As a result of this treatment, translucent pellets were obtained that had the same elasticity and smooth texture, and although they did not disintegrate when placed in the mouth, they could be easily bitten off.

[0130] (Example 18: Application of the pulverized material: Tapioca-like food) In this example, an example of producing a tapioca-like food using the macerated material of the present disclosure is shown. (material and method) 3 g of potato powder was added to 3 mL of BC β-glucan-added / disintegrated material prepared by the method of Example 2, and then kneaded, covered with plastic wrap for 30 minutes to prevent drying, and then formed into balls with a diameter of about 8 mm. This was added to 1 L of newly prepared boiling water in the same manner, treated for 2 minutes, and then picked up with chopsticks and collected on a plate.

[0131] (result) The resulting dumpling-like food product was slightly larger than before boiling, no peeling of the surface or collapse of the spherical structure was observed, and it had a chewy elasticity similar to tapioca.It did not fall apart when placed in the mouth, but could be easily bitten off.

[0132] (Example 19: Application of disintegrated material: Example of production of disintegrated material by ball mill) In this example, an example of producing a disintegrated material by a ball mill using the disintegrated material of the present disclosure will be described.

[0133] (material and method) Filter paper (Filter paper 1, Whatman) cut to a width of 1 to 2 mm and a length of approximately 30 mm 250 mg of beet pulp powder or lemon dried powder was mixed with 10 mL of water or 10 mL of 1% xyloglucan solution. The 1% xyloglucan solution was prepared in the same manner as in Example 1. The samples were crushed using a ball mill (MM301, Verder Scientific) with a 50 mL stainless steel grinding jar and a stainless steel grinding ball with a diameter of 25 mm (shaking speed 15 times / sec, 2 min).

[0134] (result) As a result, highly viscous pulverized products were obtained for all samples derived from filter paper, beet pulp powder, and lemon dry powder. Visual inspection of the pulverized filter paper showed that the samples pulverized with the xyloglucan solution were more finely dispersed than those pulverized with water.

[0135] (Example 20: Application of the disintegrated material: Tamagoyaki) In this example, an example of producing tamagoyaki (rolled egg) using the macerated material of the present disclosure is shown. (material and method) A white creamy disintegrate that was three times concentrated was obtained by centrifuging (32,300xg, 10 minutes, 4°C) the β-glucan-added disintegrate (1-3) and (1-4) obtained from BC by the method of Example 2 and collecting the precipitate. 5 mL of water (control group) or 5 g of the creamy disintegrate (test group) was added to 22.5 mL of egg liquid (yolk and white of chicken eggs dissolved without adding water) and stirred with a whisk for 2 minutes.

[0136] (result) As a result, the control group produced an egg liquid that was highly fluid and contained many small air bubbles, while the test group produced an egg liquid that was highly viscous and had few air bubbles.When tamagoyaki were made from both groups, the control group produced an egg liquid that was fluffy and easy to bite into, while the test group produced an egg liquid that was firm and elastic.

[0137] (Example 21: Application of disintegrated material: Ultra-thin solid noodle-like food that can be used with 3D food printers, etc.) In this example, an example of producing an extremely thin, firm noodle-like food product using the disintegrated material of the present disclosure is shown. (material and method) 3 mL of the β-glucan-added and disintegrated material (1-3) and (1-4) obtained from BC by the method of Example 2 was taken and mixed with 1.5 g of potato powder using a spatula, and then filled into a 10 mL plastic syringe. An adapter (a stainless steel tube narrowing the outlet of Bio-Rad's Low Pressure Fittings Kit 731-8223 to an inner diameter of 1 mm) was attached to the tip of the syringe, and then it was set in a constant-speed liquid delivery device (PicoPlus, Harvard Apparatus) and extruded at 0.5 mL / min. The paste that came out was received on a plastic tray 1.5 cm below, and the tray was manually shook back and forth and left and right to prevent it from being cut (Figure 24).

[0138] (result) The results are shown in Figure 24. The paste was arranged in a nearly straight line with an almost constant apparent diameter, without being twisted or cut into small pieces. By air-drying this paste at room temperature, an extremely thin, firm noodle-like structure was obtained that did not easily collapse.

[0139] (Example 22: Application of the disintegrated material: noodle-like food) In this example, another example of producing a noodle-like food product using the macerated material of the present disclosure is shown. (material and method) 25 mL of the (1-3) and (1-4) β-glucan-added and disintegrated material obtained from BC by the method of Example 2 was taken and heated to 100°C. Half of the mixture was added to a bowl containing 30 g of rice flour (Nihonbare, wet airflow mill) and thoroughly kneaded. 5 mL of hot water at 100°C was added and mixed, then the mixture was placed on a cooking board covered with rice starch and flattened with a stick to a thickness of 6 mm. This was cut into short noodles 6 mm wide with a knife and then placed in boiling water. When the noodles floated to the surface, heating was stopped and the mixture was immediately removed from the bowl and cooled under running water.

[0140] (result) The results are shown in Figure 25. The noodles did not crumble or break during the boiling process, and the surface was smooth, giving the noodles a firm bite.

[0141] (Example 23: Application of disintegrated material: Observation of precipitation state) In this example, the results of observing the precipitation state of the disaggregated material of the present disclosure are shown. (material and method) Soybean flour (Mitake Foods Co., Ltd.) was suspended in ion-exchanged water in a test tube to prepare a 5% (w / w) suspension (4 mL). 1 mL of ion-exchanged water or β-glucan additive / disintegrant (1-3) or (1-4) obtained from BC by the method of Example 2 was added to the suspension, stirred and suspended again, and then allowed to stand at room temperature.

[0142] (result) The results are shown in Figure 26. After 5 hours, precipitation of soybean flour was observed in the sample to which ion-exchanged water was added, whereas no precipitation was observed in the sample to which the macerated material was added.

[0143] (Example 24: Application of disintegrated material: Observation of adsorption state) In this example, the results of observing the adsorption state of the disaggregated material of the present disclosure are shown. (material and method) To 2 mL (orange) of 0.25% curcumin (Wako Pure Chemical Industries, Ltd.) dispersion in a test tube, 0.5 mL of ion-exchanged water or (1-3) or (1-4) β-glucan additive / disintegrant obtained from BC by the method of Example 2 was added and stirred. After leaving it to stand at room temperature for 5 minutes, and immediately after stirring again, 1.5 mL of the liquid was transferred to a plastic tube (2 mL capacity) and centrifuged at room temperature for 15 seconds (constant speed: CAPSULE HF-120, Tommy Seiko Co., Ltd.).

[0144] (result) As a result, in the sample to which water was added, the dispersed curcumin was found to be thinly adhered to the wall of the test tube, whereas in the sample to which the pulp was added, it was confirmed that the curcumin was adsorbed into the pulp that had solidified to the bottom by centrifugation (Figure 27).

[0145] (Example 25: Application of disintegrated material: Observation of gel state) In this example, the results of observing the gel state of the disaggregate of the present disclosure are shown. (material and method) 1 mL of water or 1 mL of the β-glucan-added / disintegrated material (1-3) or (1-4) obtained from BC by the method of Example 2 was placed in a test tube and heated to 70°C, and then 1 mL of 2% aqueous agar solution heated to 90°C was added. The mixture was immediately stirred and mixed, and then allowed to stand at room temperature for 1 hour and then cooled in air.

[0146] (result) As a result, the water-agar sample produced a transparent gel, while the lysate-agar sample produced a translucent gel. The former was brittle and crumbled in the mouth, while the latter had a good chewiness and texture.

[0147] (Example 26) 6 mL of a solution containing 50% (v / v) β-glucan-added / hybridized material (1-3) and (1-4) obtained from BC by the method of Example 2 and 1% agar, or 6 mL of 1% agar without the above hybridized material, was placed in a plastic tube and heated to 100°C to dissolve the agar, then cooled to 80°C, and 1.2 g of soybean powder was added to each tube to suspend it. When 0.5 mL of this was dropped onto a flat heat block maintained at 4°C, the tube C solidified with a width of 1.7 cm, whereas the tube S solidified with a width of 1.0 cm. When both tubes were left to stand at 80°C for 30 minutes, precipitation of soybean powder was observed in the tube without the hybridized material, but the tube containing the hybridized material maintained a suspended state.

[0148] Example 27 In this example, chitin was used as an insoluble polysaccharide and was pulverized in the presence of a water-soluble polysaccharide. It was confirmed that the complex of the present disclosure can be produced not only from cellulose and plant cell walls, but also from polysaccharides derived from crustacean shells.

[0149] 680 mg of chitin (Funakoshi, product number 82004068) was suspended in 140 mL of water or 0.2% xyloglucan aqueous solution, and ground in a household mixer for 30 seconds x 8 times following the method of Example 1. These were designated as Sample C and Sample S, respectively. Then, 32 mL of the chitin disaggregate suspension was taken out, 6.1 mL of 1% xyloglucan aqueous solution was added to Sample C, and 6.1 mL of water was added to Sample S, and both were shaken horizontally at room temperature at 100 rpm for 1 hour. Then, the fraction that passed through a 0.5 mm pore mesh was collected, and the turbidity at 600 nm was measured in a cuvette with a cell length of 1 cm, resulting in 0.20 and 0.23 for Sample C and Sample S, respectively, and the amount of particles that passed through the mesh was 15% higher for Sample S, to which xyloglucan was added during disaggregation.

[0150] (Example 28) In this example, it was confirmed that a high-density solid material composed only of glucan can be produced using the method disclosed herein. This material can also be used as a functional material in which the gelatinization properties of the starch inside can be controlled by forming a membrane on the outside to control how the material absorbs moisture.

[0151] According to the method of Example 13, 2.00 g of the white creamy disintegrated product obtained by concentrating the suspension of bacterial cellulose and (1-3) and (1-4) β-glucans according to the method of Example 20, and 2.00 g of rice starch (fine snow) were added and kneaded with a spatula for 10 minutes. This was molded into a disk shape with a diameter of about 15 mm and a height of about 8 mm, and dried in an oven at 60°C on a nylon mesh. After drying for 48 hours, 1.84 g of a disk-shaped molded product was obtained. A further 8-fold dilution of the desugared BC β-glucan-added disintegrated product used in Example 5 was applied to the periphery of this disk-shaped molded product, and the product was dried in an oven at 60°C on a nylon mesh. This molded product was removed from the oven, and a drop of water was placed on the top of the disk-shaped molded product at room temperature. The water did not penetrate into the inside and remained there even after 10 minutes (Figure 28). The extrusion product is an edible dry composition consisting only of glucan, which consists of starch, (1-3),(1-4) β-glucan and cellulose, and serves as a high-density glucose storage material with controlled water absorption behavior.

[0152] As described above, by mixing and solidifying the bacterial cellulose and (1-3) and (1-4) β-glucan-derived disaggregates with starch, a high-density glucan mass is formed, which is expected to be an edible and storage polysaccharide. In addition, since the manner in which the starch absorbs water and gelatinizes depends on the mixing condition of the disaggregate (the mobility of water, which depends on the water absorption speed of the disaggregate, and the resistance of the starch when it absorbs water and gelatinizes), it is expected that materials with new gelatinization properties can be created.

[0153] (Example 29) In this example, it was confirmed that the method disclosed herein can be used to produce a sheet from herbaceous fiber resources. After adding (1-3) and (1-4) β-glucan to the fiber obtained by alkali-treating rice straw and grinding it, this was molded into a membrane material following the method of Example 5. Previously reported (YamagishiK. et al., The RURAL(reciprocal upgrading for recycling of According to the "Agricultural Resources to Strategic Primary Products for the Rural Bioeconomy (Bioresource Technology Reports, 2020)" (Agricultural Resources to Strategic Primary Products for the Rural Bioeconomy, Bioresource Technology Reports, 2020), rice straw (Koshihikari variety) was converted into chicken manure combustion ash ( 25% w / w) and stored in a wet state for 14 days, after which it was washed with 62.5 times the amount of water relative to the dry weight of the rice straw. The rice straw after this treatment (equivalent to 0.5 g dry weight) was mixed with 19.5 mL of 0.52% (w / v) aqueous solution of β-glucan (1-3) and (1-4), placed in a stainless steel mill (Retsch, 50 mL volume, including stainless steel ball (φ2 cm)), and crushed using a ball mill (Retsch, MM-301). The crushing conditions were 15 reciprocations / second at room temperature for 4 minutes. Then, 1.5 mL of the resulting suspension was poured from the top of a 0.5 mm mesh nylon net according to the method of Example 5, and the non-passing fraction was retained. This was dried at 60°C to obtain a rice straw-paper-like membrane derived from straw (Figure 29).

[0154] As mentioned above, it is expected that resources can be transformed into general-purpose products or craft products, or molded into biomass-derived materials.

[0155] Example 30: Preparation of a complex of the present disclosure from tamarind seed gum A suspension was prepared by suspending 4 g of tamarind seed gum powder in 400 mL of ion-exchanged water and stirring while heating to 85° C. This was autoclaved for 15 minutes at 120° C., and then measuring up to 400 mL using a measuring cylinder to obtain a 1% (w / v) tamarind seed gum aqueous solution. This was diluted to 0.7%, and 40 g of the diluted solution was mixed with 100 g of desugared nata de coco, and then pulverized in a 140 mL mixer pulverization system to obtain 140 g of the complex of the present disclosure (sometimes referred to as "NP" (nata puree) in this specification).

[0156] (Example 31: Preparation of the complex of the present disclosure in a small mixer and 300 μm mesh filtration test) 27 mL of ion-exchanged water or water-soluble polysaccharide solution (0.35% solids concentration) was added to 20 g of desugared nata de coco (0.7% solids concentration) and ground for 120 seconds at room temperature using a small mixer (FML-17, Tostem). The resulting suspensions were named NPw (nata de coco desugared with water alone without adding water-soluble polysaccharides), NPxg (tamarind seed gum used as water-soluble polysaccharide), NPcmc (carboxymethylcellulose sodium salt used as water-soluble polysaccharide), and NPbx (birchwood xylan used as water-soluble polysaccharide). Each suspension was diluted 4.7 times with water to sample A, and this was passed through a 300 μm mesh to collect sample B. The absorbance at 600 nm of each sample was measured as turbidity, and the values ​​of sample A and B were used as the denominator and numerator, respectively, to represent the 300 μm mesh passing rate (%). The results are shown in Table 5. [Table 5]

[0157] (Example 32: Interaction of NPtg with various solutes) Following the method described in Example 31, 20 g of desugared nata de coco (solid concentration 0.7%) and 27 g of high-concentration tamarind seed gum solution (1.2% w / w) were mixed in a small mixer to prepare NP (NPtg). NPtg (4 g) was mixed thoroughly in a 50 mL plastic tube with 1 g of a sample in which various solutes shown in Table 6 were suspended or dissolved, and the tube was left standing upright at room temperature for 3 hours. After that, each tube was quickly turned over and laid down, and the liquid surface distance was measured after 20 seconds. The liquid surface flow distance in each solution addition area was calculated as a relative value to the water addition area (liquid surface flow distance 3.0 cm) which was the control area (liquid surface flow distance in each solution addition area (cm) / liquid surface flow distance in water addition area (3.0 cm)) × 100 (%)).

[0158] As a result, an increase or decrease in the liquid surface flow distance was observed for the added solutes listed below. This demonstrated that the physical properties of NPs can be controlled by adding various additives. In particular, the addition of galactomannan significantly reduced the fluidity, and the NPs exhibited gel-like properties with extremely low viscosity. The preparation of materials with such properties is an effective process when providing food to individuals with impaired chewing and swallowing abilities, and especially when considering automatic cooking. [Table 6]

[0159] (Example 33: Mixture of NPtg and rice flour) 500 mg of rice flour (Nipponbare, wet airflow milled product) was added to NPtg (5 g) prepared in Example 32 and dispersed, then treated at 95°C for 15 minutes. When it was taken out, a creamy food was produced (Figure 30). Since the gelatinized material after heating can be processed into a homogeneous creamy material without strong long-term stirring, this creamy food is useful as a fat-free or low-fat material when processing food such as confectionery, and can also be used as a material that can provide food to people with poor chewing and swallowing ability through a simple process using automatic operations, etc.

[0160] Example 34: Interaction of rice flour with the complex of the present disclosure (RVA) 3.0 g of rice flour (Koshihikari, wet air milled) was mixed with 2 mL of water or various complexes of the present disclosure (solid concentration from the complex: 0.14%) in an aluminum can, and then set in a Rapid Visco Analyzer (RVA, RVA4, Newport Scientific, Australia) with a paddle to measure the viscosity under standard measurement conditions and analyze the viscosity change. The measurement conditions were initial temperature 50°C, dispersion at 960 rpm for 10 seconds from the start, then 160 rpm and holding at 50°C for 1 minute, then heating to 95°C at 12°C / min, holding at 95°C for 2 minutes and 30 seconds, then cooling to 50°C at 12°C / min, and holding at 50°C for 2 minutes. Programmed viscosity measurement was performed, and the maximum viscosity and final viscosity parameters were obtained for each sample. As a result, the maximum viscosities (cP) were 4980, 5911, 5732, 5380, 5437, 5987, 5556, and 5635 for water, NPbg (using (1-3),(1-4)-β-glucan as the water-soluble polysaccharide), NPxg (using tamarind seed gum as the water-soluble polysaccharide), NPcmc (using carboxymethylcellulose sodium salt as the water-soluble polysaccharide), NPal (using sodium alginate as the water-soluble polysaccharide), NPch (using chitosan as the water-soluble polysaccharide), NPgg (using guar gum as the water-soluble polysaccharide), and NPbx (using birchwood xylan as the water-soluble polysaccharide), respectively. The final viscosities (cP) at the end of the measurement were 4204, 4609, 4359, 4432, 4893, 4307, 4262, and 4297. Thus, it was found that the complex of the present disclosure has the effect of increasing the viscosity of rice flour during and after gelatinization.

[0161] Example 35: Interaction of wheat flour with the complex of the present disclosure (RVA) In the same manner as in Example 34, 3.0 g of wheat flour (weak wheat flour, Nisshin Flour Milling Co., Ltd.) was mixed with 25 mL of water or various complexes of the present disclosure (solid concentration from the complex: 0.145%) in an aluminum can, and then set in an RVA with a paddle to analyze the viscosity change. As a result, the maximum viscosities were 1566, 2348, 2179, 1994, 1946, 2134, 2025, and 2072 for water, NPbg, NPxg, NPcmc, NPal, NPch, NPgg, and NPbx, respectively. In addition, the final viscosities (cP) at the end of the measurement were 2187, 3160, 3076, 2867, 2770, 2843, 2763, and 2811. Thus, it was found that the complex of the present disclosure has the effect of increasing the viscosity of wheat flour during and after gelatinization.

[0162] (Example 36: Dispersibility of wheat flour and rice flour) 3.1 g of weak flour (equivalent to dry weight) was mixed with 21.9 g of water or a solution in which NPw and NPxg were mixed in a ratio of 2.5% to 20% (w / w) in water, and the mixture was thoroughly stirred to form a slurry, and 10 g of the mixture was added to a glass test tube with a diameter of 15 mm. After leaving the mixture at 4°C for 18 hours, the distance (h) from the water surface to the interface of the weak flour that had settled was measured. The settling distance in the sample (water) that did not contain the complex of the present disclosure was taken as (hw), and the settling rate in each sample was taken as (h / hw) x 100 (%). A similar test was also performed using rice flour (variety: Nipponbare). As a control test, a similar test was conducted using weak flour with a polysaccharide (xanthan gum) that is commonly used as a dispersant in food. The results showed that the concentration at which NP gave dispersibility was 0.6% (w / w), which was almost the same value (13.9%) as the NPxg mixing rate of 12.5% ​​(solid concentration 0.09%, sedimentation rate 11.4%). This shows that NP gives dispersibility at a lower concentration than xanthan gum. In addition, the xanthan gum concentration at which NP gave a value (19.3%) that was similar to the rice flour sedimentation rate (11.8%) at a NPxg mixing rate of 15% (solid concentration 0.10%) was 0.5%. This shows that NP gives dispersibility at a lower concentration than xanthan gum. To compare the physical properties of the NPxg slurry and the xanthan gum slurry, we prepared weak flour with a 12.5% ​​NPxg mixing ratio, rice flour slurry with a 15% NPxg mixing ratio, weak flour containing 0.6% (w / w) xanthan gum, and rice flour slurry containing 0.5% (w / w) xanthan gum (the concentrations of weak flour and rice flour were the same (12.5% ​​(w / w)). We filled 10 mL of each into a 10 mL disposable syringe, stood the syringe with the outlet facing down, and measured the time required for 5 mL to fall naturally from the syringe. The results are shown in Figures 31 to 34.

[0163] As a result, the time for both the weak flour and rice flour was 5 seconds for the NPxg-mixed sample, whereas the time for the weak flour slurry containing 0.6% (w / w) xanthan gum was 45 seconds, and the time for the rice flour slurry containing 0.5% (w / w) xanthan gum was 82 seconds. From this, it was considered that the addition of NPxg to weak flour and rice flour dispersions is effective when high fluidity is required.

[0164] Example 37: Preparation of vegetable powder sheets / colored dots using wheat flour and the complex of the present disclosure 20g of weak flour (equivalent to dry weight) was mixed with 75g of water and 25g of NPxg to prepare a slurry, and a part of it (20g each) was mixed with 0.4g of turmeric powder (commercial product) or parsley powder (samples made by pulverizing a commercial product with a ball mill) to prepare colored pastes. The colored pastes and uncolored pastes were filled into 10mL disposable syringes and discharged onto a metal plate. Furthermore, each paste was discharged onto a heated Teflon plate, and when it seemed that the water had almost evaporated, the obtained sheet-like molded product was peeled off from the plate. The results are shown in Figures 35 and 36.

[0165] (Example 38: Addition to various vegetables and change in hardness) Commercially available cabbage powder, potato powder, soybean powder, and lemon powder were mixed with a given amount of water to prepare paste samples. The moisture content (dry matter (DM) / total weight) was set to 22.5%, 25%, 37%, and 17.5%, respectively. In addition, 100 g of paste was prepared by replacing 20% ​​of the water content with NPw or NPxg for the above samples. Three analytical samples were prepared for each paste, each containing 30 g of each paste in a plastic petri dish with a diameter of 6 cm and a height of 1 cm, and the texture profile was measured using a rheometer (Sun Scientific, CR-500DX). The main measurement parameters were a resin cylindrical plunger with a diameter of 10 mm and a height of 20 mm, which was compressed at a constant speed of 1 mm / s to a depth of 5 mm from the surface, and then the plunger was immediately pulled up in the opposite direction at the same speed. The maximum stress (N) during compression was used as an index of hardness. The measurements were repeated three times, and the average and standard deviation were calculated. The results are shown in Figure 37.

[0166] As a result, it was found that the addition of NPw and NPxg increased the hardness, and the effect was particularly remarkable in pastes to which NPxg was added. Compared to samples without added NPxg, the hardness of the cabbage, potato, soybean and lemon powder samples increased by 2.0 times, 1.7 times, 21.5 times and 2 times, respectively.

[0167] (Note) As described above, the present disclosure has been illustrated using preferred embodiments of the present disclosure, but it is understood that the scope of the present disclosure should be interpreted only by the claims. It is understood that the patents, patent applications and other documents cited in this specification should be incorporated by reference to this specification in the same manner as if the contents themselves were specifically described in this specification. This application claims priority to Japanese Patent Application No. 2021-87567 filed on May 25, 2021 with the Japan Patent Office, the contents of which are incorporated by reference in their entirety as if they constitute the contents of this application. [Industrial Applicability]

[0168] According to the present disclosure, water-insoluble carbohydrates such as cellulose, which are abundant resources, can be utilized in the food and other material fields as functional materials capable of expressing various physical properties. In particular, in the food field, low-calorie foods with various characteristics can be produced by simple processing steps, which can greatly contribute to the improvement and diversification of cooking and processing techniques. Through the development of water-insoluble carbohydrates such as cellulose in the food field, the sophistication of food expression in automatic cooking and processing processes, and the provision of meat and oil product substitutes, it is possible to contribute to both the high-level utilization of resources and the improvement of health maintenance. In addition, in the field of non-edible materials, the value of using water-insoluble carbohydrates such as cellulose-based materials can be improved through the creation of biodegradable materials, and the creation of a next-generation biological resource industry for the high-level utilization of agricultural waste, forest resources, etc. can be accelerated.

Claims

1. A fiber texture improver for foods and beverages, comprising a complex containing a water-soluble polysaccharide and a water-insoluble carbohydrate. the water-insoluble carbohydrate is disintegrated in the presence of the water-soluble polysaccharide dissolved in water, the water-insoluble carbohydrate comprises bacterial cellulose, and the water-soluble polysaccharide comprises (1-3),(1-4) β-glucan or a derivative thereof, tamarind seed gum or a derivative thereof, or any combination thereof.

2. 2. The fiber texture enhancer of claim 1, wherein the water insoluble carbohydrate is macerated by a food blender or food mixer.

Citation Information

Patent Citations

  • Redispersible microfibrillated cellulose

    JP1984189141A

  • Confectionery / Food material having pulpous palate feeling, and method for producing and using the same

    JP2001327254A

  • Thickening gelatinizer composed of three ingredients

    JP2008092914A

  • WHEAT GRANULE CONTAINING beta-GLUCAN IN HIGH CONCENTRATION

    JP2008118943A

  • Method for producing food improved in chewing and retention characteristics in mouth

    JP2008278811A